Method for producing thermoplastic resin foamed particle molded body

By filling the thermoplastic resin foamed particles with foaming layer and welding property improvement layer in the forming mold, and welding them with steam, the problems of long cooling time and poor welding property of the polypropylene resin foamed particles are solved, thereby realizing the problem of the molded body of the polypropylene resin foamed particles being long and the welding property is poor. High-efficiency and low-energy forming process.

CN118647497BActive Publication Date: 2025-02-25JSP CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380020437.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-17
Filing Date
2023-03-10
Publication Date
2025-02-25
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

In the prior art, after the filling rate of the polypropylene resin foamed particles increases, the cooling time of the molded body is significantly extended, and the weldability of the foamed particles is reduced, and there is a problem of high energy consumption.

Method used

The crack filling process is used to fill the thermoplastic resin foamed particles with foaming layer and welding improvement layer in the forming mold, and steam is supplied to the cavity after the forming mold is completely closed, so that the foamed particles are welded to each other and form a high filling rate. And a molded body with excellent surface properties.

Benefits of technology

The polypropylene-based resin foamed particle molded body with excellent productivity, excellent surface properties and welding properties is achieved, which shortens the cooling time in the mold and the drying time after demolding, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118647497B_ABST
    Figure CN118647497B_ABST
Patent Text Reader

Abstract

A method for manufacturing a thermoplastic resin foamed particle molded body includes a crack filling step and an in-mold molding step. The foamed particles (2) used in the crack filling step have a columnar shape and have one or more defective parts selected from a group consisting of through holes and grooves, or two of them. The ratio Ca / A of the average cross-sectional area Ca of each defective part to the average cross-sectional area A of the foamed particles (2) in the cut surface obtained by cutting the foamed particles (2) at the center of the axial direction with a plane perpendicular to the axial direction is greater than 0.01 and less than 0.20, and the ratio Ct / A of the total cross-sectional area Ct of the defective parts to the average cross-sectional area A of the foamed particles (2) is greater than 0.02 and less than 0.20. When the molding die (1) is completely closed, the filling rate F of the foamed particles (2) is greater than 125% and less than 220%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a thermoplastic resin foamed particle molded body. Background Art

[0002] Polypropylene resin foamed particle molded bodies are used for various purposes such as packaging materials, containers, and cushioning materials because they are lightweight and have excellent cushioning properties and rigidity. In recent years, the use of polypropylene resin foamed particle molded bodies has been increasingly expanded, and along with this, there is a demand for forming polypropylene resin foamed particles into various shapes.

[0003] The polypropylene resin foamed bead molded body is manufactured, for example, by filling the polypropylene resin foamed beads into a forming mold and then supplying steam into the forming mold for heating. In the in-mold forming method, if steam is supplied into the forming mold, the foamed beads are foamed for a second time and their surfaces melt. As a result, the foamed beads in the forming mold are mutually welded, and a molded body having a shape corresponding to the shape of the cavity of the forming mold can be obtained. The molded body just after being formed is easy to expand due to the secondary foaming, so it is demolded from the forming mold after cooling with water, air, etc. in the forming mold. Since the molded body after demolding contains moisture from the steam, it is used for various purposes after being fully dried.

[0004] In the in-mold forming method, when the foaming particles are not filled into the forming mold sufficiently, the appearance of the obtained molded body is easy to deteriorate. Therefore, as a method for filling the polypropylene resin foaming particles into the forming mold as tightly as possible, there is a method called crack filling (for example, refer to patent document 1). In the crack filling, the forming mold is not completely clamped, but after the foaming particles are filled into the cavity in a state where the movable mold is slightly retreated from the fixed mold to the mold opening direction, the forming mold is clamped, thereby mechanically compressing the foaming particles in the cavity. Crack filling does not require special equipment, so it is a method generally adopted in the in-mold forming method.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2020 / 189389 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The polypropylene resin foamed beads described in Patent Document 1 have the problem that the cooling of the molded body in the molding die requires a significantly longer time when the filling rate of the foamed beads is increased. In addition, if the filling rate of the foamed beads is increased, the weldability of the foamed beads is easily reduced.

[0010] In addition, with the improvement of environmental awareness in recent years, it is expected to reduce energy consumption in the manufacturing process of molded bodies. From this point of view, it is also expected to further shorten the cooling time in the mold and the drying time after demolding to improve the productivity of molded bodies with excellent surface properties and weldability.

[0011] The present invention has been made in view of the above background, and an object of the present invention is to provide a method for producing a thermoplastic resin foamed bead molded article that is excellent in productivity and has excellent surface properties and weldability.

[0012] Means used to solve problems

[0013] One aspect of the present invention is a method for producing a thermoplastic resin foamed bead molded article according to the following [1] to

[11] .

[0014] [1] A method for producing a thermoplastic resin foamed particle molded body, wherein:

[0015] The method for producing the thermoplastic resin foamed particle molded body comprises:

[0016] a crack filling step of filling the molding cavity of the molding die with the crack gap opened with thermoplastic resin foamed particles having a foam layer, and then completely closing the molding die; and

[0017] In the in-mold forming process, after the crack filling process is completed, steam is supplied into the forming cavity to fuse the foamed particles to each other.

[0018] The foamed particles have a columnar shape and have one or more defective parts selected from the group consisting of a through hole penetrating the inside thereof in the axial direction and a groove extending in the axial direction on the side circumference thereof,

[0019] The ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed beads in the cross-sectional surface obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction is 0.01 or more and 0.20 or less, and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed beads is 0.02 or more and 0.20 or less,

[0020] In a state where the forming mold is completely closed, the filling rate F of the foamed beads represented by the following formula (1) is 125% or more and 220% or less,

[0021] F={a / (b×c)}×100···(1)

[0022] Wherein, a in the formula (1) is the mass of the foamed particles filled in the forming mold (unit: kg), and b is the bulk density of the foamed particles (unit: kg / m 3 ), c is the volume of the forming cavity (unit: m 3 ).

[0023] [2] The method for producing a thermoplastic resin foamed particle molded article according to [1], wherein the average length L of the molding cavity in the opening and closing direction of the molding die represented by the following formula (2) is: A 10 mm or more and 200 mm or less,

[0024] L A =V / S···(2)

[0025] Wherein, V in the formula (2) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ).

[0026] [3] The method for producing a thermoplastic resin foamed bead molded article according to [1] or [2], wherein a ratio of the apparent density of the foamed beads to the bulk density of the foamed beads is greater than 1.6 and less than 2.0.

[0027] [4] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [3], wherein the foamed beads have one or more through holes as the defective portion.

[0028] [5] A method for producing a thermoplastic resin foamed particle molded body according to any one of [1] to [4], wherein the foamed particles have a foaming layer and a weldability improving layer covering the foaming layer, the base resin of the foaming layer is a first thermoplastic resin, and the base resin of the weldability improving layer is a second thermoplastic resin.

[0029] [6] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [5], wherein the thermoplastic resin constituting the foamed layer is a polyolefin-based resin.

[0030] [7] The method for producing a thermoplastic resin foamed particle molded body according to any one of [1] to [6], wherein the thermoplastic resin constituting the foamed layer is an ethylene-propylene random copolymer having an ethylene component content of 0.5 mass % or more and 3.5 mass % or less.

[0031] [8] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [7], wherein the bulk density of the foamed beads is 10 kg / m 3 Above and 50kg / m 3 the following.

[0032] [9] The method for producing a thermoplastic resin foamed bead molded article according to any one of [1] to [8], wherein the porosity of the thermoplastic resin foamed bead molded article obtained by the production method is 4% or more and 12% or less.

[0033]

[10] A method for producing a thermoplastic resin foamed bead molded body according to any one of [1] to [9], wherein the crack filling step is performed using the foamed beads that are not given an internal pressure or the foamed beads that are given an internal pressure of less than 0.1 MPa (G).

[0034]

[11] The method for producing a thermoplastic resin foamed particle molded article according to any one of [1] to

[10] , wherein when the molding die is completely closed, the maximum value P of the compression ratio represented by the following formula (3) is max is 25% or more and 120% or less,

[0035] P max =(δ / L min )×100···(3)

[0036] Wherein, δ in the formula (3) is the size of the gap of the forming die (unit: mm), L min It is the minimum value (unit: mm) of the length of the molding cavity in the opening and closing direction when the molding die is completely closed.

[0037] Effects of the Invention

[0038] According to the above aspect, it is possible to provide a method for producing a thermoplastic resin foamed bead molded article that is excellent in productivity and can mold a molded article having excellent surface properties and weldability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a cross-sectional view of the forming mold in a state where the foamed beads are filled in the crack filling step.

[0040] Figure 2 This is a schematic diagram of the appearance of a foamed bead having a through hole as a defective portion.

[0041] Figure 3 yes Figure 2 Cross-sectional view taken along line III-III (top view of the cut surface of the foamed particles).

[0042] Figure 4 This is a schematic diagram showing the appearance of a foamed bead having a groove as a defective portion.

[0043] Figure 5 yes Figure 4 Cross-sectional view taken along the VV line (top view of the cut surface of the foamed particles).

[0044] Figure 6 This is a schematic diagram showing the appearance of expanded beads having a weldability-improving layer.

[0045] Figure 7 yes Figure 6 Cross-sectional view taken along line VII-VII (top view of the cut surface of the foamed particles).

[0046] Figure 8 It is an explanatory diagram showing a method of calculating the area of ​​the high temperature peak. DETAILED DESCRIPTION

[0047] (Method for producing thermoplastic resin foamed particle molded article)

[0048] When manufacturing the thermoplastic resin foamed bead molded body (hereinafter referred to as "foamed bead molded body" or "molded body"), first, a crack filling step is performed, in which thermoplastic resin foamed beads (hereinafter referred to as "foamed beads") having a foam layer are filled into the molding cavity of the molding die in a state where the crack gap is opened, and then the molding die is completely closed. For example, Figure 1 As shown, the forming mold 1 for manufacturing the formed body has a fixed mold 11 and a movable mold 13, the movable mold 13 is configured to form a forming cavity 12 between the fixed mold 11, and the movable mold 13 is configured to be able to reciprocate in one direction relative to the fixed mold 11. In addition, hereinafter, the moving direction of the movable mold is sometimes referred to as the "opening and closing direction". The forming cavity provided in the forming mold has a shape corresponding to the shape of the desired formed body.

[0049] The foamed particles filled in the forming mold have a columnar shape and have one or more defects selected from a group consisting of a through hole that penetrates the inside in the axial direction and a groove that extends in the axial direction on the side circumference. In addition, the ratio of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed particles in the cross-section obtained by cutting the foamed particles in the center of the axial direction with a plane perpendicular to the axial direction is greater than 0.01 and less than 0.20, and the ratio of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed particles is greater than 0.02 and less than 0.20. In addition, the detailed structure of the foamed particles will be described later.

[0050] In the crack filling step, the foamed particles are filled into the forming mold, for example, in the following manner. Figure 1 As shown, the movable mold 13 is arranged at a position where the forming cavity 12 is formed and is separated from the fixed mold 11 in the opening and closing direction, and a crack gap is formed between the movable mold 13 and the fixed mold 11. At this time, the crack gap is formed so that the foamed particles 2 do not leak out from the forming cavity 12 to the outside. Then, the foamed particles 2 are filled into the forming cavity 12 in a state where the forming mold 1 is not completely closed. In a state where the foamed particles 2 are filled into the forming cavity 12, the foamed particles 2 are not compressed by the forming mold 1, and the shape of the natural state is maintained.

[0051] After the filling of the foamed particles 2 into the forming cavity 12 is completed, the movable mold 13 is moved toward the fixed mold 11 to close the forming mold 1. When the forming mold 1 is completely closed, the foamed particles 2 in the forming cavity 12 are mechanically compressed in the opening and closing direction by the movable mold 13. In the manufacturing method, the foamed particles are filled in a manner such that the filling rate F of the foamed particles represented by the following formula (1) is 125% or more and 220% or less in the state where the forming mold is completely closed.

[0052] F={a / (b×c)}×100···(1)

[0053] Wherein, a in the formula (1) is the mass of the foamed particles filled in the forming mold (unit: kg), and b is the bulk density of the foamed particles (unit: kg / m 3 ), c is the volume of the forming cavity (unit: m 3 ).

[0054] After the crack filling process is performed as described above, an in-mold forming process is performed, in which steam is supplied into the forming cavity to fuse the foamed particles to each other. In the in-mold forming process, the foamed particles in the forming mold are heated by steam, and are secondary foamed and fused to each other. Thus, the foamed particles in the forming mold can be integrated to form a molded body.

[0055] After the foamed beads are heated, the molded body in the mold is cooled with water or the like to stabilize its shape. Then, the molded body is removed from the mold to complete the in-mold molding.

[0056] In the manufacturing method, the foamed particles having the specific shape are filled into the molding cavity in such a manner that the filling rate F is within the specific range. In this way, by setting the filling rate F to a relatively large range and then performing in-mold molding using steam after performing crack filling, the drying time of the molded body after demolding can be easily shortened, and the productivity of the molded body can be significantly improved. In addition, in the manufacturing method, since the foamed particles have the specific shape, the cooling time of the molded body in the molding die can be shortened, and even in the case where the thickness of the molded body is relatively thick or the molded body has a complex shape such as a shape including parts with different thicknesses, the surface properties and weldability of the molded body can be improved. Furthermore, in the manufacturing method, even in the case where the molded body after demolding from the molding die is not subjected to a curing process, it is easy to suppress significant shrinkage and deformation of the molded body. As reasons for obtaining such an effect, for example, the following reasons can be considered.

[0057] As described above, the foamed particles have one or more defective parts selected from the group consisting of grooves and through holes. It is believed that if such foamed particles are used to fill the cracks in the above manner, the defective parts of the foamed particles such as through holes and grooves, the gaps between the foamed particles, etc. are complexly connected in the state of completely closing the forming mold, thereby forming a fine passage through which steam can pass in the forming cavity. Therefore, it is believed that when steam is supplied to the forming mold, the steam easily reaches the inside of the forming mold via the fine passage, and the foamed particles in the forming mold can be easily heated as a whole. In addition, it is believed that the foamed particles with the defective parts have moderate secondary foaming properties, so they expand moderately when heated by steam. As a result, it is believed that by using the foamed particles, even under the condition of low molding temperature during in-mold molding, the weldability is excellent, and a molded body with a good appearance can be obtained.

[0058] In addition, the foamed particles having the defective portion have moderate secondary foaming properties, so that even when the internal pressure is not applied in advance or the applied internal pressure is relatively low, secondary foaming can be fully performed in the forming mold. Furthermore, it is believed that since the foamed particles have the above-mentioned defective portion, excessive expansion of the formed body at the time point when the heating with steam is completed can be avoided. As a result, the time required from the completion of the heating of the foamed particles to the stabilization of the shape of the formed body in the forming mold can be shortened. As a result, it is believed that the time required for cooling the formed body in the forming mold can be shortened. In addition, even when the filling rate F is relatively large within the above-mentioned range, the weldability of the formed body can be improved and the cooling time during in-mold forming can be shortened.

[0059] Furthermore, a moderate open cell structure is formed in the molded body after the in-mold molding is completed. The open cell structure is a tiny space portion that is connected to the outside of the molded body. The open cell structure is formed by the gaps between the foamed particles being connected, the continuous cell portions of the foamed particles constituting the molded body, and the defective portions, etc. being complexly connected. It is believed that according to the manufacturing method, the formation of a coarse open cell structure inside the molded body can be suppressed, so that the time required for drying the molded body after demolding can be shortened.

[0060] In addition, it is believed that when the molded body having an open cell structure is taken out from the mold, air quickly flows into the cells inside the molded body through the open cell structure, and as a result, the internal pressure of the molded body is stabilized at an early stage. Therefore, it is believed that according to the above-mentioned production method, it is easy to suppress significant shrinkage and deformation of the molded body even when a curing step is not performed.

[0061] When using foamed beads without defective parts for crack filling and in-mold forming, there are risks of poor welding between the foamed beads, increased cooling time of the molded body in the forming mold, and significant deterioration in productivity. These problems are particularly likely to occur when the thickness of the molded body to be obtained is thick or the filling rate F during crack filling is high.

[0062] In addition, even in the case of defective parts, when the ratio Ca / A of the average cross-sectional area Ca of each defective part to the average cross-sectional area A of the foamed particles and / or the ratio Ct / A of the total cross-sectional area Ct of the defective parts to the average cross-sectional area A of the foamed particles is too small, it is difficult to obtain the effect brought by the defective parts. Therefore, there is a risk of poor welding between the foamed particles. In addition, in this case, the cooling time of the molded body in the forming mold becomes too long, and there is a risk of reduced productivity. In addition, if the curing process is not performed, there is a risk of significant shrinkage and deformation of the molded body.

[0063] By using foamed particles having a Ca / A ratio of 0.01 or more and a Ct / A ratio of 0.02 or more, the cooling time of the molded body in the molding die can be shortened. From the viewpoint of further improving the effect of this action, the Ca / A ratio is preferably 0.02 or more. From the same viewpoint, the Ct / A ratio is more preferably 0.03 or more.

[0064] On the other hand, when the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed particles and / or the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed particles is too large, there is a risk of reducing the secondary foaming property of the foamed particles. As a result, larger voids are easily formed in the resulting molded body, which may lead to an increase in moisture content and an increase in drying time. In addition, when the filling rate F during crack filling is low, in addition to these problems, there is a risk of causing a deterioration in the surface properties (appearance) of the molded body and a reduction in rigidity.

[0065] By using foamed particles having a ratio of Ca / A of less than 0.20 and a ratio of Ct / A of less than 0.20, the drying time of the molded body after demolding can be shortened, and a molded body with excellent surface properties and rigidity can be easily obtained. From the viewpoint of more reliably obtaining these effects, the ratio Ca / A is preferably less than 0.15, more preferably less than 0.10, and further preferably less than 0.08. From the same viewpoint, the ratio Ct / A is preferably less than 0.18, more preferably less than 0.15, further preferably less than 0.10, and particularly preferably less than 0.08. In addition, the calculation method for the average cross-sectional area A of the foamed particles, the average cross-sectional area Ca of each defective portion, and the total cross-sectional area Ct of the defective portion is described later.

[0066] When forming the preferred range of the value of the ratio Ca / A, the upper limit and lower limit of the above-mentioned ratio Ca / A can be arbitrarily combined. For example, the preferred range of the value of the ratio Ca / A can be above 0.02 and below 0.15, or above 0.02 and below 0.10, or above 0.02 and below 0.08. Similarly, when forming the preferred range of the value of the ratio Ct / A, the upper limit and lower limit of the above-mentioned Ct / A can be arbitrarily combined. For example, the preferred range of the value of the ratio Ct / A can be above 0.03 and below 0.18, or above 0.03 and below 0.15, or above 0.03 and below 0.10, or above 0.03 and below 0.08.

[0067] Furthermore, in the crack filling step, by filling the expanded beads so that the filling rate F of the expanded beads represented by the following formula (1) is 125% or more and 220% or less, the above-mentioned effects can be reliably obtained.

[0068] F={a / (b×c)}×100···(1)

[0069] Wherein, a in the formula (1) is the mass of the foamed particles filled in the forming mold (unit: kg), and b is the bulk density of the foamed particles (unit: kg / m 3), c is the volume of the forming cavity (unit: m 3 ).

[0070] If the filling rate F of the expanded beads in the crack filling process is too low, there is a risk of increasing the moisture content of the molded body and increasing the drying time. From the viewpoint of more reliably avoiding these problems, the filling rate F of the expanded beads in the crack filling process is preferably 130% or more, and more preferably 135% or more.

[0071] On the other hand, when the filling rate F in the crack filling process is too high, it is difficult for steam to spread throughout the forming mold in the in-mold forming process, which may lead to reduced weldability, deterioration of the surface properties (appearance) of the formed body, and reduced rigidity. In addition, in this case, it is difficult to suppress the shrinkage and deformation of the formed body when the curing process is omitted. From the viewpoint of more reliably avoiding these problems, the filling rate of the foamed particles in the crack filling process is preferably 200% or less, more preferably 180% or less, and further preferably 150% or less.

[0072] When forming the preferred range of the filling rate F in the crack filling step, the upper limit value and the lower limit value of the filling rate F described above can be arbitrarily combined. For example, the preferred range of the filling rate F can be 130% or more and 200% or less, 130% or more and 180% or less, or 135% or more and 150% or less.

[0073] The filling rate F of the foamed beads can be adjusted by, for example, changing the shape of the foamed beads, the size of the crack gap δ (unit: mm) during in-mold molding, and the maximum value P of the compression rate described later. max etc. to adjust. The size of the gap δ (unit: mm) is as follows Figure 1 As shown in FIG. 1 , it is the distance in the opening and closing direction from the fixed mold 11 to the movable mold 13 when the foamed particles 2 are completely filled into the molding cavity 12. In addition, the size of the crack gap δ is also equal to the movement amount in the opening and closing direction of the movable mold 13 from the state where the foamed particles 2 are completely filled into the molding cavity 12 to the state where the molding mold 1 is completely closed.

[0074] In the manufacturing method, preferably, when the forming die is completely closed, the maximum value P of the compression ratio represented by the following formula (3) is max It is 25% or more and 120% or less.

[0075] P max =(δ / L min )×100···(3)

[0076] Among them, L in the above formula (3) minIt is the minimum value (unit: mm) of the length of the molding cavity in the opening and closing direction when the molding die is completely closed.

[0077] In the manufacturing method, even if the maximum compression ratio P max Since the foamed beads have a predetermined defective portion, the water cooling time during in-mold molding can be shortened. In addition, as described above, the defective portion or the like becomes a passage for steam, so it is easier to obtain a molded body with a high fusion rate. max In the above range, the drying time of the molded body can be further shortened.

[0078] From the viewpoint of further shortening the drying time of the molded body, the maximum value P of the compression rate of the foamed beads is max On the other hand, from the viewpoint of further improving the weldability between the foamed particles and more reliably suppressing the shrinkage and deformation of the molded body when the curing step is omitted, the maximum value P of the compression rate of the foamed particles is max It is more preferably 100% or less, further preferably 80% or less, and particularly preferably 50% or less.

[0079] The maximum value P of the compression ratio of the foamed particles max When the preferred range is set, the maximum compression ratio P mentioned above can be arbitrarily combined. max For example, the maximum compression ratio P max The preferred range of may be 30% to 100%, 30% to 80%, or 35% to 50%.

[0080] In the manufacturing method, an internal pressure imparting step of imparting internal pressure to the foamed particles before filling into the forming mold may be performed as required. However, as described above, the foamed particles have moderate secondary foaming properties, so even if the magnitude of the internal pressure imparted in the internal pressure imparting step is further reduced or the internal pressure imparting step is omitted, a good molded body can be easily obtained. In addition, by further reducing the magnitude of the internal pressure imparted in the internal pressure imparting step or omitting the internal pressure imparting step, the time required for the internal pressure imparting step can be reduced, and the productivity of the foamed particle molded body can be further improved.

[0081] When the internal pressure imparting process is performed, the internal pressure of the foamed particles filled in the forming mold can be set to, for example, 0.1 MPa (G) (G: gauge pressure) or less, preferably 0.08 MPa (G) or less. In addition, from the perspective of the productivity of the foamed particle molded body, it is particularly preferred to perform the molding without imparting internal pressure to the foamed particles. In addition, the pressure (internal pressure) in the bubble can be measured, for example, by the method described in Japanese Patent Gazette No. 2003-201361.

[0082] In the manufacturing method, the specific method of forming the cavity is not particularly limited, and can be set in a manner corresponding to the shape of the desired molded body. Figure 1 As shown, the molding cavity 12 can be configured to mold a rectangular parallelepiped molded body. In addition, although not shown, the molding cavity can also be configured to mold a bottomed box-shaped molded body, a molded body having portions with different thicknesses, and the like.

[0083] From the viewpoint of making the above-mentioned effects more effective, the average length L of the molding cavity in the opening and closing direction of the molding die expressed by the following formula (2) is: A The average length L of the molding cavity in the opening and closing direction is preferably 10 mm or more, more preferably 15 mm or more, and even more preferably 20 mm or more. A The upper limit is approximately 500 mm, preferably 300 mm, more preferably 200 mm, and further preferably 150 mm.

[0084] L A =V / S···(2)

[0085] Wherein, V in the formula (2) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ).

[0086] The average length L in the opening and closing direction of the molding cavity A When the preferred range is A For example, the average length L A The preferred range of may be 10 mm to 300 mm, 10 mm to 200 mm, 15 mm to 200 mm, or 15 mm to 150 mm.

[0087] By setting the average length L of the forming cavity A By setting the above specific range, the average thickness and L can be obtained. AIn addition, the manufacturing method has the above-mentioned effect, so according to the manufacturing method, even if the average length L of the molding cavity is A For example, even when the diameter is relatively large within the above range such as 55 mm or more, a good molded body can be obtained.

[0088] In the in-mold forming process, the foamed particles are heated by supplying steam into the forming cavity. The forming temperature during in-mold forming can be controlled by the forming pressure, that is, the pressure of the steam supplied into the forming cavity. If the forming temperature (i.e., the forming pressure) during in-mold forming is increased, the foamed particles are easily welded to each other, but on the other hand, there is a tendency for the cooling time in the forming mold to be longer. On the other hand, if the forming temperature is reduced, the cooling time in the forming mold can be shortened, but on the other hand, there is a tendency for the foamed particles to be difficult to weld to each other. From the viewpoint of the production efficiency of the formed body, it is preferably formed with a forming pressure as low as possible. From this viewpoint, the forming pressure is, for example, preferably in the range of 0.18MPa(G) or more and 0.30MPa(G) or less in the range of 0.22MPa(G) or more and 0.28MPa(G) or less in the range of 0.28MPa(G) or less in the range of 0.22MPa(G) or more in the range of 0.28MPa(G) or less in the range of 0.28MPa(G) or less in the range of 0.28MPa(G) or less in the range of 0.18MPa(G) or more in the range of 0.30MPa(G) or less ...

[0089] In the manufacturing method, a curing step of allowing the molded body to stand for a predetermined time in a high temperature atmosphere adjusted to, for example, about 60° C. to 80° C. may be performed as needed. However, even if the molded body is not subjected to the curing step in a high temperature atmosphere, shrinkage and deformation of the molded body can be suppressed. When the curing step is omitted, for example, the molded body can be stabilized in shape by allowing the molded body to stand for 12 hours or more in an environment of, for example, 23° C.

[0090] (Foamed particle molded body)

[0091] The molded body obtained by the manufacturing method has an open cell structure. The open cell structure is a tiny space portion connected to the outside of the molded body. The open cell structure is formed by the interconnection of multiple defective parts of the foamed particles such as through holes and grooves, the connection of defective parts of the foamed particles with the voids formed between the foamed particles, the connection of voids between the foamed particles, and the continuous cell parts of the foamed particles constituting the molded body.

[0092] The compact density is preferably 10 kg / m 3 Above and 150kg / m 3 In this case, the lightness and rigidity of the molded body can be improved in a balanced manner. From the viewpoint of further improving the rigidity of the molded body, the density of the molded body is more preferably 15 kg / m 3 More preferably, 20 kg / m 3From the viewpoint of further improving the lightness of the molded body, the density of the molded body is more preferably 60 kg / m 3 Below, more preferably 50kg / m 3 Below, particularly preferably 45kg / m 3 The density of the molded body is calculated by dividing the mass of the molded body (unit: g) by the volume (unit: L) obtained from the outer dimensions of the molded body and converting the units. In addition, for example, when the molded body has a complex shape at least in part and the volume is not easy to obtain from the outer dimensions of the molded body, the volume of the molded body can be obtained by water.

[0093] When forming the preferred range of the molded body density, the upper limit and lower limit of the molded body density mentioned above can be arbitrarily combined. For example, the preferred range of the molded body density can be 10 kg / m 3 Above and 60kg / m 3 Below, can also be 15kg / m 3 Above and 50kg / m 3 Below, can also be 20kg / m 3 Above and 45kg / m 3 the following.

[0094] In the past, when manufacturing a molded body with a low density, the molded body tends to deform significantly after demolding, so it is particularly difficult to omit the curing step. In contrast, the foamed bead molded body can omit the curing step even when the density is low, and even without curing, it has a desired shape and excellent appearance and rigidity. From the viewpoint of effectively exerting this effect, it is also preferred that the density of the molded body is set to the above range.

[0095] From the viewpoint of being able to more reliably obtain the effect of suppressing significant shrinkage and deformation of the molded body without performing the curing step, the porosity of the molded body is preferably 4% or more, more preferably 5% or more. In addition, from the viewpoint of further improving the rigidity and appearance of the molded body, the porosity of the molded body is preferably 12% or less, more preferably 10% or less, and further preferably 8% or less.

[0096] When forming the preferred range of the porosity of the molded body, the above upper and lower limits of the porosity may be arbitrarily combined. For example, the preferred range of the porosity of the molded body may be 5% to 10%, or 5% to 8%.

[0097] The porosity of the formed body is measured and calculated, for example, as follows. Specifically, first, a test piece of a rectangular shape (for example, 20 mm long × 100 mm wide × 20 mm high) is cut out from the center of the formed body. Next, the test piece is sunk into a measuring cylinder filled with ethanol, and the true volume Vc (unit: L) of the test piece is calculated from the amount of rise in the liquid level of ethanol. In addition, the apparent volume Vd (unit: L) is calculated from the outer dimensions of the test piece. The porosity (unit: %) of the formed body is expressed by the following formula (4) using the true volume Vc and apparent volume Vd of the test piece obtained as described above.

[0098] Void ratio = [(Vd-Vc) / Vd] × 100 (4)

[0099] The molded article can also be used as a sound absorbing material, a shock absorbing material, a cushioning material, and the like in various fields such as the vehicle field such as automobiles and the construction field.

[0100] (Thermoplastic resin foam particles)

[0101] The foamed particles used in the manufacturing method have a columnar shape and have one or more defective parts selected from the group consisting of a through hole that axially penetrates the inside of the foamed particles and a groove that extends axially on the side circumference of the foamed particles. If the foamed particles have defective parts, it is easier to form an open cell structure in the molded body.

[0102] <Foamed particles having through holes>

[0103] Figure 2 as well as Figure 3 An example of the foamed beads 2 having the through-holes 211 as the defective portions 21 is shown. Figure 2 The foamed beads 2 shown have a cylindrical shape with through holes 211. The overall shape of the foamed beads can be, for example, a cylindrical shape or a prism shape. The through holes preferably penetrate the axial direction of the foamed beads. The number of through holes can be one or more.

[0104] In the case where the foamed particles have the through holes as defective portions, the average pore size d of the through holes is preferably greater than 0.1 mm and less than 1 mm. In this case, the Ca / A and / or Ct / A of the foamed particles can be easily adjusted to the above range. By setting the average pore size d of the through holes to greater than 0.1 mm, it is possible to prevent the through holes of the foamed particles from being flattened and clogged during in-mold molding, and the effect of the through holes can be more reliably exerted. From the same point of view, the average pore size d of the through holes is more preferably greater than 0.2 mm, and further preferably greater than 0.4 mm.

[0105] On the other hand, when the average pore size d of the through hole is too large, there is a hidden danger that the Ca / A and / or Ct / A of the foamed particles become too large. Therefore, there is a hidden danger that the drying of the molded body requires too much time. In addition, there is a hidden danger that the gaps between the foamed particles, the concave-convex of the through hole, etc. are easily formed on the surface of the molded body, and there is a hidden danger that the rigidity of the molded body is reduced. In addition, if the filling rate F of the foamed particles is further increased in order to avoid the formation of gaps between the foamed particles, the concave-convex of the through hole, etc., there is a hidden danger that the density of the molded body becomes significantly higher and it is difficult to obtain a lightweight molded body. In addition, if the filling rate F is further increased, there is a hidden danger that the molding temperature required to obtain a good molded body becomes significantly higher. In addition, in this case, when the curing process is omitted, there is a hidden danger that the significant shrinkage and deformation of the molded body cannot be suppressed. These problems can be easily avoided by setting the average pore size d of the through hole to less than 1mm. From the same point of view, the average pore size d of the through hole is more preferably less than 0.95mm, more preferably less than 0.9mm, and particularly preferably less than 0.85mm.

[0106] When constituting the preferred range of the average pore size d of the through hole, the upper limit and lower limit of the above-mentioned average pore size d can be arbitrarily combined. For example, the preferred range of the average pore size d can be 0.2 mm or more and 0.95 mm or less, 0.2 mm or more and 0.9 mm or less, or 0.4 mm or more and 0.85 mm or less.

[0107] The average pore size d of the through-holes 211 of the foamed beads 2 is obtained as follows. First, the foamed beads 2 are cut at the center of the axial direction with a plane perpendicular to the axial direction, as shown in FIG. Figure 3 The cut surface is exposed as shown. Next, a photograph of the cut surface is taken, and the cross-sectional area (specifically, the opening area) of the through hole in the cut surface is calculated. Then, the diameter of an imaginary perfect circle having the same area as the cross-sectional area of ​​the through hole is calculated, and this value is used as the pore size of the through hole of each foamed particle. The above operation is performed on more than 50 foamed particles, and the arithmetic mean of the pore size of the through hole obtained is used as the average pore size d of the through hole of the foamed particles. In addition, even if the size of the through hole of each foamed particle is such that the through hole diameter is different in the through direction, the through hole diameter of each foamed particle is determined by the pore diameter of the through hole in the cut surface as described above.

[0108] The average pore size d of the through holes can be adjusted to the specific range by adjusting the size of the average pore size dr of the through holes in the resin particles described later, the apparent density of the foamed particles, etc. In addition, by making the foamed particles into secondary foamed particles produced by secondary foaming, the average pore size d can be more easily adjusted to a small value.

[0109] From the viewpoint of increasing the wall thickness of the foamed beads to improve the secondary foaming property of the foamed beads and the rigidity of the molded body, and from the viewpoint of being able to more reliably suppress the deformation and shrinkage of the molded body when the curing process is omitted, the average outer diameter D of the foamed beads is preferably 2 mm or more, more preferably 2.5 mm or more, and further preferably 3 mm or more. On the other hand, from the viewpoint of improving the filling property of the foamed beads into the molding die, the average outer diameter D of the foamed beads is preferably 8 mm or less, more preferably 5 mm or less, and further preferably 4.5 mm or less.

[0110] When constituting the preferred range of the average outer diameter D of the foamed beads, the upper limit and lower limit of the above-mentioned average outer diameter D can be arbitrarily combined. For example, the preferred range of the average outer diameter D can be 2 mm or more and 8 mm or less, 2.5 mm or more and 5 mm or less, or 3 mm or more and 4.5 mm or less.

[0111] The ratio d / D of the average pore size d of the through-holes to the average outer diameter D of the foamed particles is preferably 0.4 or less, more preferably 0.35 or less, further preferably 0.3 or less, and particularly preferably 0.25 or less. By making the ratio d / D 0.4 or less, the secondary foaming property of the foamed particles during in-mold forming can be appropriately improved, and a molded body with excellent surface properties and rigidity can be more easily obtained. On the other hand, with regard to d / D, from the viewpoint of further suppressing the through-holes of the foamed particles from being flattened and blocked during in-mold forming and more reliably exerting the effect of the through-holes, the ratio d / D is preferably 0.1 or more. In addition, the calculation method of the average outer diameter D of the foamed particles will be described later.

[0112] When forming the preferred range of the value of the ratio d / D, the upper limit and lower limit of the above ratio d / D can be arbitrarily combined. For example, the preferred range of the value of the ratio d / D can be 0.1 or more and 0.4 or less, 0.1 or more and 0.35 or less, 0.1 or more and 0.3 or less, or 0.1 or more and 0.25 or less.

[0113] The average wall thickness t of the foamed particles with through holes is preferably 1.0 mm or more and 2.0 mm or less. If the average wall thickness t is within this range, the wall thickness of the foamed particles is thick enough, so the secondary foaming property during in-mold forming is further improved. In addition, the foamed particles are less likely to be flattened relative to external forces, and the rigidity of the molded body is further improved. From this viewpoint, the average wall thickness t of the foamed particles is more preferably 1.2 mm or more.

[0114] The average wall thickness t of the foamed beads is the distance from the surface of the foamed beads (ie, the outer surface) to the outer edge of the through-hole (ie, the inner surface of the foamed beads), and is a value obtained by the following formula (5).

[0115] t=(Dd) / 2···(5)

[0116] d: average diameter of through holes (unit: mm)

[0117] D: Average outer diameter of foamed particles (unit: mm)

[0118] In addition, the ratio t / D of the average wall thickness t of the foamed particles relative to the average outer diameter D is preferably greater than 0.30 and less than 0.50. If t / D is within the above range, the filling property of the foamed particles becomes better during the in-mold forming of the foamed particles. In addition, the water cooling time can be maintained shorter, and the secondary foaming property can be further improved. Thus, a molded body with excellent appearance and rigidity can be manufactured with good productivity at a lower forming heating temperature. From this viewpoint, the ratio t / D of the average wall thickness t of the foamed particles relative to the average outer diameter D is more preferably greater than 0.32, and more preferably greater than 0.35.

[0119] <Foamed particles having grooves>

[0120] Figure 4 as well as Figure 5 An example of the foamed beads 2 having the grooves 212 as the defective portions 21 is shown. Figure 4 The foamed particles 2 shown have a columnar shape and have at least one groove 212 on the side circumference thereof.

[0121] The above-mentioned "groove" refers to a concave portion provided on the side circumference of the foamed bead 2 and extending along the axial direction of the foamed bead 2. More specifically, Figure 5 As shown, the groove 212 of the foamed bead 2 is observed as a portion where the outline of the foamed bead 2 is recessed inward in a cross section obtained when the foamed bead 2 is cut along a plane perpendicular to the axial direction of the foamed bead 2 .

[0122] The shape of the foamed particles 2 can be various. Figure 4 as well as Figure 5 As shown, the foamed bead 2 may be a columnar shape having a cross-shaped cross section perpendicular to the axial direction. The foamed bead 2 having such a shape has four grooves 212 on its side surface. The cross-sectional shape of the foamed bead in the cross section perpendicular to the axial direction is not limited to Figure 4 as well as Figure 5 The shape can be, for example, a shape based on a circle, a shape based on a triangle, a shape based on a quadrilateral, or the like.

[0123] The number of grooves 212 provided in the foamed beads may be one or more. Figure 4 as well as Figure 5The V-shape shown may be in various forms such as a semicircular shape, a quadrilateral shape, and a U-shape. When the foamed beads have two or more grooves 212, all the grooves 212 may have the same cross-sectional shape or different cross-sectional shapes.

[0124] The foamed beads preferably have 2 or more and 6 or less grooves. In this case, it is easier to form an open cell structure in the molded body. Therefore, even if the curing step is omitted, the molded body is less likely to deform.

[0125] In addition, when the foamed beads have two or more grooves, the grooves are preferably arranged at equal intervals on the side circumference of the foamed beads. In other words, when the foamed beads have multiple grooves, the grooves are preferably arranged at positions symmetrical with respect to the central axis of the foamed beads. If such foamed beads are molded in-mold, it is easier to form an open bubble structure in the molded body. Therefore, even if the curing step is omitted, the molded body is less likely to deform.

[0126] <Average cross-sectional area Ca and total cross-sectional area Ct per defect>

[0127] In the cross section obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction, the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed beads is 0.01 or more and 0.20 or less, and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed beads is 0.02 or more and 0.20 or less. As described above, in the manufacturing method, by using the foamed beads having the specific shape, the productivity of the molded body can be significantly improved, and a molded body with excellent surface properties and weldability can be easily obtained.

[0128] The method for calculating the average cross-sectional area A of the foamed beads is as follows. First, the foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. The cross-sectional area of ​​the foamed beads 2 in the cut surface is measured. For example, Figure 3 as well as Figure 5 When the foamed beads 2 are composed of only the foamed layer 3 as shown in FIG. 1 , the cross-sectional area of ​​the foamed beads 2 is equal to the cross-sectional area of ​​the foamed layer 3 in the cut surface. Figure 7 When the foamed particle 2 has a foamed layer 3 and a weldability improving layer 4 covering the foamed layer 3 as shown, the cross-sectional area of ​​the foamed particle 2 is the sum of the cross-sectional area of ​​the foamed layer 3 in the cut surface and the cross-sectional area of ​​the weldability improving layer 4. In addition, the cross-sectional area of ​​the foamed particle 2 in the cut surface can be measured, for example, by taking a photograph of the cut surface of the foamed particle and performing image analysis. In addition, the cross-sectional area of ​​the defective portion is not included in the cross-sectional area of ​​the foamed particle.

[0129] The above operation is performed for 100 or more expanded beads, and the arithmetic mean value of the cross-sectional areas of the obtained expanded beads is defined as the average cross-sectional area A of the expanded beads in the cut surface.

[0130] The average cross-sectional area Ca of each defect and the total cross-sectional area Ct of the defects are calculated as follows. First, the foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. Figure 3 as well as Figure 7 When the defective portion 21 is a through hole 211 as shown, the cross-sectional area C of the through hole 211 in the cut surface is measured.

[0131] In addition, when the defect 21 is a groove 212, as shown in FIG. Figure 5 As shown in FIG. 1 , a tangent line L1 is drawn on the outside of each groove 212 in the cut surface, which is tangent to the outline of the foamed bead 2 at two points Q1 and Q2 and does not pass through the inside of the foamed bead 2. Then, the area of ​​the region surrounded by the outline of the foamed bead 2 and the tangent line L1 is calculated, and the area is taken as the cross-sectional area C of each groove 212. That is, the cross-sectional area C of each groove 212 is Figure 5 The area of ​​the region indicated by the diagonal line.

[0132] By summing up the cross-sectional areas C of the through-holes 211 and the cross-sectional areas C of the grooves 212 thus obtained, the total cross-sectional areas of the defects 21 in each foamed bead 2 are calculated. In addition, the cross-sectional area of ​​each defect in each foamed bead 2 is calculated by dividing the total cross-sectional areas of the defects 21 by the number of defects 21.

[0133] The above operation is performed for 100 or more expanded beads, and the arithmetic mean of the total cross-sectional areas of the obtained defects is taken as the total cross-sectional area Ct of the defects. Also, the average cross-sectional area of ​​each defect is taken as the average cross-sectional area Ca of each defect.

[0134] The method for calculating the average outer diameter D of the foamed beads is as follows. First, the foamed beads 2 are cut at the center of the axial direction with a plane perpendicular to the axial direction, so that Figure 3 as well as Figure 5The cut surface as shown in the figure is exposed. Two points Q3 and Q4 with the longest distance between each other are determined on the outline of the foamed particle 2 in the cut surface, and the distance between these two points (that is, the maximum outer diameter of the foamed particle in the cut surface) is taken as the outer diameter r of each foamed particle 2. Then, the arithmetic mean of the outer diameters r measured for more than 100 foamed particles 2 is taken as the average outer diameter D of the foamed particles. In addition, the measurement of the outer diameter of the foamed particles 2 in the cut surface can be performed, for example, by taking a photograph of the cut surface of the foamed particles and performing image analysis. In addition, even if the outer diameters of the foamed particles are different in the through-direction, the outer diameter of each foamed particle is determined by the outer diameter at the cut surface as described above.

[0135] <Apparent density and bulk density of foamed particles>

[0136] The bulk density of the foamed particles is preferably 10 kg / m 3 Above and 50kg / m 3 Below, more preferably 20kg / m 3 Above and 35kg / m 3 In this case, the lightness and rigidity of the molded body can be improved in a balanced manner. In addition, in the past, especially when manufacturing a molded body with a low density (i.e., a molded body with a high molded body ratio), the molded body is easily deformed after demolding, and it is difficult to omit the curing process. In contrast, the foamed particles can omit the curing process even when the apparent density is low, so a molded body with a good appearance can be manufactured even without curing.

[0137] The ratio of the apparent density of the foamed particles to the bulk density of the foamed particles (i.e., apparent density / bulk density) is preferably greater than 1.6, and more preferably greater than 1.7. In this case, the cooling time after in-mold molding can be further shortened, and a lightweight and good foamed particle molded body can be more easily obtained. In addition, the deformation and shrinkage of the molded body when the curing process is omitted can be more reliably suppressed. In addition, the ratio of the apparent density of the foamed particles to the bulk density of the foamed particles (i.e., apparent density / bulk density) is preferably less than 2.0, and more preferably less than 1.9. In this case, the drying time of the molded body can be further shortened. In addition, the surface properties and rigidity of the obtained molded body can be made better.

[0138] When constituting the preferred range of the value of the ratio of the apparent density of the foamed beads to the bulk density of the foamed beads, the upper limit and lower limit of the above ratio can be arbitrarily combined. For example, the preferred range of the value of the apparent density / bulk density can be 1.7 or more and less than 2.0, or 1.7 or more and 1.9 or less.

[0139] The calculation method of the bulk density of the foamed particles is as follows. First, the foamed particles are allowed to stand for more than 24 hours in an environment with a relative humidity of 50%, a temperature of 23°C, and an air pressure of 1 atm to adjust the state of the foamed particles. The foamed particle group after the state adjustment is filled into a measuring cylinder in a naturally stacked manner, and the bulk volume of the foamed particle group (unit: L) is read from the scale of the measuring cylinder. Then, by converting the value obtained by dividing the mass of the foamed particle group in the measuring cylinder (unit: g) by the above-mentioned bulk volume, the bulk density of the foamed particles (unit: kg / m 3 ). The bulk density of the expanded particles is a value measured using the expanded particles in a natural state without being compressed under an environment with an air pressure of 1 atm.

[0140] The method for calculating the apparent density of the foamed particles is as follows. First, the foamed particle group is allowed to stand for 1 day in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed particles. After measuring the mass (unit: g) of the foamed particle group, use a metal mesh to sink it into a measuring cylinder filled with alcohol (such as ethanol) at 23°C, and calculate the volume (unit: L) of the foamed particle group from the amount of liquid level rise. Thereafter, the apparent density (unit: kg / m 3 ).

[0141] <Foaming layer>

[0142] The foamed particles have a foaming layer with a thermoplastic resin as a base resin. The thermoplastic resin constituting the foaming layer is preferably a crystalline thermoplastic resin with crystallinity such as a polyolefin resin, a polyamide resin, and a crystalline polyester resin, etc., such as a polypropylene resin and a polyethylene resin. In addition, in this specification, a polypropylene resin refers to a homopolymer of a propylene monomer and a propylene copolymer containing more than 50% by mass of a structural unit from propylene. In addition, a polyethylene resin refers to a homopolymer of an ethylene monomer and an ethylene copolymer containing more than 50% by mass of a structural unit from ethylene.

[0143] In addition, in this specification, polyamide resin refers to polyamide and polyamide copolymer. When the base material resin of the foaming layer is a polyamide resin, the polyamide resin constituting the foaming layer is preferably a polyamide copolymer. As a polyamide copolymer, for example, polycaprolactam / polyhexamethylene adipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminodipic acid / lauryl lactam (nylon 6 / 66 / 12) and caprolactam / lauryl lactam copolymer (nylon 6 / 12) etc. can be cited.

[0144] In the present specification, "having crystallinity" means that the endothermic peak heat quantity associated with melting of the resin obtained by using a DSC curve at a heating rate of 10°C / min using a heat flux differential scanning calorimeter according to "when the heat of fusion is measured after a certain heat treatment" described in JIS K7122 (1987) (the heating rate and cooling rate in the state adjustment of the test piece are both set to 10°C / min) is 5 J / g or more. The endothermic peak heat quantity is preferably 15 J / g or more, and more preferably 30 J / g or more.

[0145] The foaming layer may contain other polymers other than the thermoplastic resin within the range that does not hinder the above-mentioned effects. As other polymers, elastomers and the like may be exemplified. The content of other polymers in the foaming layer is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 0, i.e., the foaming layer substantially contains only thermoplastic resin as the polymer.

[0146] In addition, the thermoplastic resin as the base resin of the foaming layer may contain additives such as a bubble regulator, a crystal nucleating agent, a flame retardant, a flame retardant aid, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet light blocking agent, a light stabilizer, a conductive filler, an antibacterial agent, and a colorant within the range that does not impair the above-mentioned effects. The content of the additive in the foaming layer is preferably 0.01 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the thermoplastic resin.

[0147] The thermoplastic resin constituting the foaming layer is preferably a polyolefin resin. In addition, the thermoplastic resin constituting the foaming layer is preferably a polypropylene resin among polyolefin resins, and more preferably a propylene copolymer formed by copolymerization of propylene and other monomers. In this case, the content of other polymers other than the polypropylene resin in the foaming layer is preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, and particularly preferably 0, that is, the foaming layer substantially contains only the polypropylene resin as a polymer.

[0148] As the propylene copolymer, preferably, ethylene-propylene copolymer, butene-propylene copolymer, hexene-propylene copolymer, ethylene-propylene-butene copolymer and the like copolymer of propylene and α-olefin having 4 to 10 carbon atoms can be exemplified. These copolymers can be, for example, random copolymers or block copolymers, preferably random copolymers. In addition, the foaming layer can contain one polypropylene resin or two or more polypropylene resins.

[0149] The thermoplastic resin constituting the foaming layer is particularly preferably an ethylene-propylene random copolymer containing ethylene components of more than 0.5 mass % and less than 3.5 mass % among these polypropylene resins. According to the foaming particles having such a foaming layer, it is possible to more easily obtain a molded body having excellent in-mold formability, excellent rigidity and excellent surface properties, and capable of suppressing deformation and shrinkage even when the curing process is omitted. In addition, in this case, the secondary foaming property of the foaming particles can be further improved, and the curing process can be omitted even when using foaming particles that are not given internal pressure or foaming particles that are given an internal pressure less than 0.1MPa (G).

[0150] From the viewpoint of further improving the moldability of the expanded beads and obtaining a molded article having excellent energy absorption properties, the content of the ethylene component in the ethylene-propylene random copolymer is preferably 2.0% by mass or more and 3.5% by mass or less.

[0151] In addition, the above-mentioned "ethylene component" and "propylene component" refer to the structural unit derived from ethylene and the structural unit derived from propylene in the ethylene-propylene copolymer, respectively. In addition, the content of the ethylene component is the mass ratio of the ethylene component when the total of the ethylene component and the propylene component is set to 100% by mass. The content of each component in the ethylene-propylene copolymer can be obtained based on the result of IR spectrum measurement.

[0152] When the base resin of the foaming layer is a polypropylene resin, the melting point Tmc of the polypropylene resin is preferably below 155°C. In this case, a molded body with excellent appearance and rigidity can be formed at a lower molding temperature (i.e., a low molding pressure). From the viewpoint of improving this effect, the melting point Tmc of the polypropylene resin constituting the foaming layer is preferably below 150°C, and more preferably below 145°C. On the other hand, from the viewpoint of further improving the heat resistance and mechanical strength of the molded body, the melting point Tmc of the polypropylene resin constituting the foaming layer is preferably above 135°C, more preferably above 138°C, and further preferably above 140°C.

[0153] When constituting the preferred range of the melting point Tmc value of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the melting point Tmc described above may be arbitrarily combined. For example, the preferred range of the melting point Tmc may be 135°C to 155°C, 138°C to 150°C, or 140°C to 145°C.

[0154] In the case where the thermoplastic resin constituting the foaming layer is crystalline, the melting point of the thermoplastic resin can be determined based on the obtained DSC curve by differential scanning calorimetry (i.e., DSC) according to JIS K7121-1987. First, the state of the test piece is adjusted according to "(2) After a certain heat treatment, the melting temperature is measured". The state-adjusted test piece is heated from 30°C to 200°C at a heating rate of 10°C / min, thereby obtaining a DSC curve, and the vertex temperature of the melting peak appearing in the DSC curve is taken as the melting point Tmc of the thermoplastic resin. In addition, in the case where multiple melting peaks appear in the DSC curve, the vertex temperature of the melting peak with the largest area is taken as the melting point Tmc.

[0155] When the base resin of the foaming layer is a polypropylene resin, the melt mass flow rate (i.e., MFR) of the polypropylene resin is preferably 5 g / 10 minutes or more, more preferably 6 g / 10 minutes or more, and further preferably 7 g / 10 minutes or more. In this case, the foamability and formability can be further improved. On the other hand, from the viewpoint of further improving the rigidity of the molded body, the MFR of the polypropylene resin is preferably 12 g / 10 minutes or less, and more preferably 10 g / 10 minutes or less. In addition, the MFR of the polypropylene resin is a value measured based on JIS K7210-1:2014 under the conditions of a test temperature of 230°C and a load of 2.16 kg.

[0156] When constituting the preferred range of MFR of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the above-mentioned MFR can be arbitrarily combined. For example, the preferred range of MFR can be 5 g / 10 minutes or more and 12 g / 10 minutes or less, 6 g / 10 minutes or more and 12 g / 10 minutes or less, or 7 g / 10 minutes or more and 10 g / 10 minutes or less.

[0157] When the base resin of the foaming layer is a polypropylene resin, the bending elastic modulus of the polypropylene resin is preferably 800 MPa or more and 1600 MPa or less. From the viewpoint of improving the rigidity of the molded body and more reliably suppressing the dimensional change when the curing process is omitted, the bending elastic modulus of the polypropylene resin constituting the foaming layer is preferably 800 MPa or more, more preferably 850 MPa or more, and further preferably 900 MPa or more. On the other hand, from the viewpoint of being able to mold a molded body with excellent appearance and rigidity at a lower molding temperature (i.e., low molding pressure) and obtaining a foamed particle molded body with excellent energy absorption characteristics, the bending elastic modulus of the polypropylene resin constituting the foaming layer is preferably less than 1200 MPa, more preferably 1100 MPa or less, and further preferably 1000 MPa or less. In addition, the bending elastic modulus of the polypropylene resin can be obtained based on JIS K7171:2008.

[0158] When constituting the preferred range of the bending elastic modulus of the polypropylene resin constituting the foaming layer, the upper limit and lower limit of the above-mentioned bending elastic modulus can be arbitrarily combined.For example, from the viewpoint of improving the rigidity of the formed body, more reliably suppressing the viewpoint of the dimensional change under the situation of omitting the curing process, the bending elastic modulus of the polypropylene resin constituting the foaming layer can be more than 850MPa and less than 1600MPa, or more than 900MPa and less than 1600MPa.In addition, from the viewpoint of being able to form the formed body of outward appearance, excellent rigidity under lower forming temperature (that is, low forming pressure), the viewpoint of the foamed particle formed body that obtains excellent energy absorption characteristics, the bending elastic modulus of the polypropylene resin constituting the foaming layer can be more than 800MPa and less than 1200MPa, or more than 800MPa and less than 1100MPa, or more than 800MPa and less than 1000MPa.

[0159] In the past, especially when foamed beads made of a polypropylene resin having a bending elastic modulus of less than 1200 MPa were molded in-mold, the molded body after demolding tended to shrink and deform significantly if the curing step was omitted, probably because the resistance to shrinkage and deformation after demolding was small. In contrast, according to the above-mentioned method for manufacturing a molded body, for example, even when foamed beads made of a polypropylene resin having a bending elastic modulus of less than 1200 MPa are used, shrinkage and deformation of the molded body can be easily suppressed, and the curing step can be omitted.

[0160] When the base resin of the foaming layer is a polyamide resin, the bending modulus of the polyamide resin is preferably 800 MPa or more and 1600 MPa or less, and more preferably 1000 MPa or more and 1600 MPa or less. If the bending modulus of the polyamide resin is within the above range, it is different from the amide elastomer having a bending modulus of about 600 MPa or less. Even if it is exposed to room temperature after foaming, it is not easy to shrink, and it is easy to obtain foamed particles with a small apparent density. In addition, it is possible to more reliably suppress the dimensional change when the curing process is omitted. In addition, the bending modulus of the polyamide resin can be obtained based on JIS K7171: 2008. In addition, the melting point of the polyamide resin is preferably 180°C or more and 250°C or less.

[0161] In addition, when the base resin of the foaming layer is a polyamide resin, the melt mass flow rate (i.e., MFR) of the polyamide resin measured under the conditions of a test temperature of 230° C. and a load of 2.16 kg according to JIS K7210-1:2014 is preferably 1 g / 10 min or more and 8 g / 10 min or less, and more preferably 2 g / 10 min or more and 5 g / 10 min or less. In this case, the foamability and moldability can be further improved.

[0162] <Weldability Improvement Layer>

[0163] Alternatively, the foamed particles may include a foaming layer and a fusion-improving layer covering the foaming layer, and may have a multilayer structure in which the base resin of the foaming layer is a first thermoplastic resin and the base resin of the fusion-improving layer is a second thermoplastic resin. In this case, the fusion-improving layer may cover the entire surface of the foaming layer or may cover a portion of the foaming layer. For example, Figure 6 as well as Figure 7 As shown, the weldability improving layer 4 may be provided on the side peripheral surface of the foamed beads 2 and cover the foamed layer 3 .

[0164] The weldability improving layer is a layer provided on the surface of the foamed particles in order to improve the weldability of the foamed particles in the in-mold forming. The second thermoplastic resin constituting the weldability improving layer preferably has a melting point or a low softening point lower than the melting point of the first thermoplastic resin as the base resin of the foaming layer. In addition, when the second thermoplastic resin constituting the weldability improving layer is a crystalline thermoplastic resin of the same type as the first thermoplastic resin constituting the foaming layer, the second thermoplastic resin preferably has a crystallinity lower than that of the first thermoplastic resin. By coating the foaming layer with such a thermoplastic resin, the foamed particles can be welded at a lower forming temperature (i.e., a low forming pressure) in the in-mold forming. As a result, the deformation and shrinkage of the molded body in the case where the curing process is omitted can be more reliably suppressed.

[0165] The second thermoplastic resin constituting the weldability improving layer may be a crystalline thermoplastic resin or a non-crystalline thermoplastic resin. As the crystalline thermoplastic resin used in the weldability improving layer, for example, polyolefin resins can be exemplified. In addition, as the non-crystalline thermoplastic resin used in the weldability improving layer, for example, polystyrene resins can be exemplified. In the case where the foaming layer is composed of a polypropylene resin, from the viewpoint of adhesion to the foaming layer, the second thermoplastic resin constituting the weldability improving layer is preferably a polyolefin resin, more preferably a polyethylene resin and / or a polypropylene resin, and further preferably a polypropylene resin. As the polypropylene resin used as the second thermoplastic resin, for example, ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-propylene-butene copolymers, and propylene homopolymers can be cited. Among them, as the base resin of the weldability improving layer, ethylene-propylene copolymers and / or ethylene-propylene-butene copolymers are particularly preferably used.

[0166] When the second thermoplastic resin constituting the weldability improving layer is a crystalline thermoplastic resin, the difference Tmc-Tms between the melting point Tmc of the first thermoplastic resin constituting the foaming layer and the melting point Tms of the second thermoplastic resin constituting the weldability improving layer is preferably 5°C or more, more preferably 6°C or more, and even more preferably 8°C or more. In this case, the weldability of the foamed particles can be further improved, and the molding temperature can be further reduced. On the other hand, from the viewpoint of suppressing the peeling of the foaming layer and the weldability improving layer, the mutual adhesion between the foamed particles, etc., the difference Tmc-Tms between the melting point Tmc and the melting point Tms is preferably 35°C or less, more preferably 20°C or less, and even more preferably 15°C or less. The melting point of the second thermoplastic resin used in the weldability improving layer is determined based on JIS K7121:1987. More specifically, the melting point of the second thermoplastic resin used in the weldability improving layer can be determined by the same conditions and method as the first thermoplastic resin constituting the above-mentioned foaming layer.

[0167] When constituting the preferred range of the melting point difference Tmc-Tms value, the upper limit and lower limit of the melting point difference Tmc-Tms described above may be arbitrarily combined. For example, the preferred range of the melting point difference Tmc-Tms may be 5°C to 35°C, 6°C to 20°C, or 8°C to 15°C.

[0168] The calculation method of the crystallinity of the above-mentioned thermoplastic resin is as follows. First, DSC is performed based on JIS K7122-1987, and the heat of crystallization of the thermoplastic resin is calculated based on the obtained DSC curve. Specifically, the state of the thermoplastic resin is adjusted according to "(2) After a certain heat treatment, the melting temperature is measured." In the state adjustment, the thermoplastic resin is heated from 23°C to 200°C at a heating rate of 10°C / min, and then the temperature of 200°C is maintained for 10 minutes to melt the thermoplastic resin. Thereafter, the thermoplastic resin is cooled from 200°C to 23°C at a cooling rate of 10°C / min. After the state adjustment is performed in the above manner, the thermoplastic resin is heated from 23°C to 200°C at a heating rate of 10°C / min, and the DSC curve during the second heating is obtained. The area of ​​the crystallization peak appearing in the DSC curve is calculated, and the heat of fusion is calculated from the value. The value of the ratio of the heat of fusion obtained in this way to the heat of fusion of complete crystallization expressed as a percentage is defined as the crystallinity of the thermoplastic resin (unit: %).

[0169] In addition, when the second thermoplastic resin constituting the weldability improving layer is a non-crystalline thermoplastic resin, the difference Tmc-Tss between the melting point Tmc of the first thermoplastic resin constituting the foaming layer and the softening point Tss of the second thermoplastic resin constituting the weldability improving layer is preferably 5°C or more, more preferably 6°C or more, and even more preferably 8°C or more. In this case, the weldability of the foamed particles can be further improved and the molding temperature can be further reduced. On the other hand, from the viewpoint of suppressing the peeling of the foaming layer and the weldability improving layer, the mutual adhesion between the foamed particles, etc., the difference Tmc-Tss between the melting point Tmc and the softening point Tss is preferably 35°C or less, more preferably 20°C or less. The softening point of the non-crystalline thermoplastic resin used in the weldability improving layer is the Vicat softening point measured by the A50 method based on JIS K7206:1999.

[0170] When forming the preferred range of the difference Tmc-Tss value, the upper limit and lower limit of the difference Tmc-Tss described above can be arbitrarily combined. For example, the preferred range of the difference Tmc-Tss may be 5°C to 35°C, 6°C to 20°C, or 8°C to 20°C.

[0171] The second thermoplastic resin constituting the weldability improving layer may contain additives such as a crystal nucleating agent, a flame retardant, a flame retardant aid, a plasticizer, an antistatic agent, an antioxidant, an ultraviolet light blocking agent, a light stabilizer, a conductive filler, an antibacterial agent, and a colorant, within a range not impairing the above-mentioned effects. The content of the additive in the weldability improving layer is preferably 0.01 parts by mass or more and 10 parts by mass or less, for example, relative to 100 parts by mass of the thermoplastic resin.

[0172] The weldability improving layer of the foamed particles may be in a foamed state or a non-foamed state, but is preferably in a substantially non-foamed state. "Substantially non-foamed" means a state in which the weldability improving layer is not foamed and does not contain bubbles, and a state in which bubbles disappear after foaming, and there is almost no bubble structure. The thickness of the weldability improving layer is, for example, 0.5 μm or more and 100 μm or less. In addition, an intermediate layer may be further provided between the foaming layer and the weldability improving layer.

[0173] From the viewpoint of maintaining the rigidity of the molded body and improving the moldability, the mass ratio (mass %) of the resin constituting the foaming layer to the resin constituting the weldability improving layer is preferably foaming layer: weldability improving layer = 99.5:0.5 to 80:20, more preferably 99:1 to 85:15, and further preferably 97:3 to 88:12.

[0174] When the thermoplastic resin constituting the foaming layer is a crystalline thermoplastic resin, the foamed particles preferably have a crystal structure as follows: in the DSC curve obtained when heated from 23°C to 200°C at a heating rate of 10°C / min, an endothermic peak caused by melting inherent to the crystalline thermoplastic resin constituting the foaming layer and one or more melting peaks located at a position closer to the high temperature side than the endothermic peak appear. Foamed particles having such a crystal structure have excellent mechanical strength and excellent formability. In addition, hereinafter, the endothermic peak caused by melting inherent to the crystalline thermoplastic resin appearing in the DSC curve is referred to as a "resin inherent peak", and the melting peak that appears at a position closer to the high temperature side than the resin inherent peak is referred to as a "high temperature peak". The resin inherent peak is generated by the endothermic absorption of the crystals originally possessed by the crystalline thermoplastic resin constituting the foaming layer when they melt. On the other hand, it is presumed that the high temperature peak is generated by the melting of secondary crystals formed in the crystalline thermoplastic resin constituting the foaming layer during the manufacturing process of the foamed particles. That is, it is presumed that when a high temperature peak appears in the DSC curve, secondary crystals are formed in the crystalline thermoplastic resin.

[0175] Whether the expanded beads have the above-mentioned crystal structure can be determined based on a DSC curve obtained by differential scanning calorimetry (DSC) under the above-mentioned conditions in accordance with JIS K7121: 1987. When performing DSC, 1 to 3 mg of the expanded beads can be used as a sample.

[0176] Specifically, in the DSC curve obtained when heating from 23°C to 200°C at a heating rate of 10°C / min as described above (i.e., the first heating), both the high temperature peak and the resin intrinsic peak of the crystalline thermoplastic resin constituting the foaming layer appear. In addition, in the DSC curve obtained when the first heating is performed, on the basis of the high temperature peak, the resin intrinsic peak also appears. In contrast, after the first heating, the DSC curve obtained when cooling from 200°C to 23°C at a cooling rate of 10°C / min and then heating from 23°C to 200°C (i.e., the second heating) at a heating rate of 10°C / min is observed only in the DSC curve obtained when the foaming layer is formed. Thus, by comparing the DSC curve obtained when the first heating is performed with the DSC curve obtained when the second heating is performed, the resin intrinsic peak and the high temperature peak can be distinguished. The temperature of the top of the resin intrinsic peak is sometimes slightly different in the first heating and the second heating, but the difference is usually within 5°C.

[0177] From the viewpoint of further improving the moldability of the foamed particles and obtaining a molded body with better rigidity, the heat of fusion of the high temperature peak of the foamed particles is preferably from 5 J / g to 40 J / g, more preferably from 7 J / g to 30 J / g, and even more preferably from 10 J / g to 20 J / g.

[0178] The heat of fusion of the high temperature peak is determined as follows: First, 1 to 3 mg of the conditioned foamed beads are used as a sample and subjected to differential scanning calorimetry at a heating rate of 10°C / min from 23°C to 200°C to obtain a DSC curve. Figure 8 An example of a DSC curve is shown. In the case where the foamed particles have a high temperature peak, such as Figure 8 As shown, in the DSC curve, there appear a resin-specific peak ΔH1 and a high-temperature peak ΔH2 having a peak at a higher temperature side than the peak of the resin-specific peak ΔH1.

[0179] Next, a straight line L2 is drawn connecting point α corresponding to 80°C on the DSC curve and point β corresponding to the melting end temperature T of the foamed beads. The melting end temperature T is the end point on the high temperature side of the high temperature peak ΔH2, that is, the intersection of the high temperature peak ΔH2 in the DSC curve and the baseline on the high temperature side of the high temperature peak ΔH2.

[0180] After the straight line L2 is drawn, a straight line L3 is drawn which passes through the maximum point γ between the resin-specific peak ΔH1 and the high-temperature peak ΔH2 and is parallel to the vertical axis of the graph. The resin-specific peak ΔH1 and the high-temperature peak ΔH2 are divided by the straight line L3. The endothermic amount of the high-temperature peak ΔH2 can be calculated based on the area of ​​the portion constituting the high-temperature peak ΔH2 in the DSC curve, the straight line L2, and the portion surrounded by the straight line L3.

[0181] (Method for producing foamed particles)

[0182] The foamed particles can be produced, for example, by dispersing thermoplastic resin particles (hereinafter referred to as "resin particles") using a thermoplastic resin as a base resin in a dispersion medium, impregnating the resin particles with a foaming agent, and then releasing the resin particles containing the foaming agent together with the dispersion medium under low pressure. In addition, such a foaming method is sometimes referred to as a "direct foaming method".

[0183] Resin particles can be produced, for example, by a wire cutting method. In the wire cutting method, first, a thermoplastic resin as a base resin of a foaming layer and additives such as a bubble nucleating agent supplied as needed are supplied into an extruder, heated, and kneaded to form a resin melt kneaded product. Afterwards, the resin melt kneaded product is extruded from a small hole of a die head attached to the front end of the extruder to form an extrudate. After the extrudate is cooled, it is cut into a desired length, thereby obtaining a resin particle having a single-layer structure consisting of a core layer with a thermoplastic resin as a base resin.

[0184] In the case of foamed particles having a multilayer structure with a foaming layer and a weldability-improving layer, a coextrusion device having a core layer forming extruder, a weldability-improving layer forming extruder, and a coextrusion die connected to the two extruders is used to produce resin particles of the multilayer structure. In this case, in the core layer forming extruder, a first thermoplastic resin as a base material resin of the foaming layer and additives added as required are melt-kneaded to produce a core layer forming resin melt-kneaded product. In addition, in the weldability-improving layer forming extruder, a second thermoplastic resin as a base material resin of the weldability-improving layer and additives added as required are melt-kneaded to produce a weldability-improving layer forming resin melt-kneaded product.

[0185] These resin melt kneading products are coextruded and merged in a die head to form a composite of a multilayer structure consisting of a columnar core layer in a non-foamed state and a non-foamed weldability improving layer covering the outer surface of the core layer. The composite is extruded from a small hole in the die head to form an extrudate. After the extrudate is cooled, it is cut into a desired length to obtain resin particles of a multilayer structure. In addition, the manufacturing method of the resin particles is not limited to the above method, and a thermal cutting method, an underwater cutting method, etc. can also be used.

[0186] In the direct foaming method, the resin particles are foamed while roughly maintaining the shape of the resin particles. Therefore, the shape of the foamed particles obtained by the direct foaming method is roughly the shape of the resin particles after enlarging the shape. Therefore, in the case of wanting to obtain a cylindrical foamed particle with a through hole, the cylindrical resin particles with a through hole can be foamed. Such resin particles can be manufactured, for example, by using a die head with a small hole of a ring corresponding to the shape of the cut surface of the desired resin particle in the above-mentioned wire cutting method.

[0187] Similarly, when it is desired to obtain foamed particles having a cross-shaped cross section in the cut surface, it is sufficient to foam columnar resin particles having a cross-shaped cross section in the cut surface. Such resin particles can be produced, for example, by using a die head having a cross-shaped small hole corresponding to the shape of the cut surface of the desired resin particles in the above-mentioned wire cutting method.

[0188] When making resin particles, it is preferred to adopt a wire cutting method in which the cylindrical extrudate is cooled in water and then cut. In this case, the accuracy of the shape of the resin particles can be further improved, and the shape of the defective part in the finally obtained foamed particles can be more easily formed into a desired shape.

[0189] The particle size of the resin particles is preferably 0.1 mm to 3.0 mm, more preferably 0.3 mm to 1.5 mm. The ratio of the length to the outer diameter of the resin particles is preferably 0.5 to 5.0, more preferably 1.0 to 3.0.

[0190] In addition, the average mass of each resin particle is preferably 0.1 mg or more and 20 mg or less, more preferably 0.2 mg or more and 10 mg or less, further preferably 0.3 mg or more and 5 mg or less, and particularly preferably 0.4 mg or more and 2 mg or less. In addition, the average mass of each resin particle is the value obtained by dividing the mass of 200 randomly selected resin particles by the number of resin particles.

[0191] When the resin pellet has a core layer and a weldability improving layer, the mass ratio of the core layer to the weldability improving layer is preferably core layer: weldability improving layer = 99.5:0.5 to 85:15, more preferably 99:1 to 92:8, and further preferably 97:3 to 90:10.

[0192] In the foamed particles having through holes, by adjusting the average pore size dr of the through holes of the core layer in the resin particles, the average pore size d of the through holes of the foamed layer can be adjusted to the specific range. More specifically, by making the average pore size dr of the through holes of the resin particles be 0.10 mm or more and less than 0.25 mm, preferably 0.12 mm or more and less than 0.24 mm, more preferably 0.15 mm or more and less than 0.22 mm, it is possible to easily manufacture foamed particles having an average pore size d of the through holes of 0.1 mm or more and less than 1 mm. The average pore size dr of the through holes of the core layer of the resin particles can be adjusted, for example, by the pore size of the small hole of the die head used to form the through holes (i.e., the inner diameter of the die head).

[0193] In addition, by adjusting the particle size and average mass of the resin particles, the average outer diameter of the foamed particles can be adjusted to the above range. More specifically, by making the ratio dr / Dr of the average pore size dr of the through holes of the resin particles to the average outer diameter Dr be 0.4 or less, preferably 0.3 or less, more preferably 0.25 or less, and further preferably 0.2 or less, it is possible to easily manufacture foamed particles in which the ratio d / D of the average pore size d of the through holes of the foamed particles to the average outer diameter D is 0.4 or less. In addition, from the viewpoint of the manufacturing stability of the resin particles, the average pore size dr of the through holes of the resin particles is preferably 0.1 mm or more, and the ratio dr / Dr of the average pore size dr of the through holes of the resin particles to the average outer diameter Dr is preferably 0.1 or more.

[0194] The method for calculating the average pore diameter dr of the through holes of the resin particles and the average outer diameter Dr of the resin particles is the same as the method for calculating the average pore diameter d of the through holes of the foamed beads and the average outer diameter D of the foamed beads described above, except that resin particles are used instead of the foamed beads.

[0195] In addition, when a wire cutting method is used for cutting the extrudate, that is, a method in which a cylindrical extrudate extruded from a die is pulled while being cooled in water and then cut into an appropriate length, the particle size, length / outer diameter ratio and average mass of the resin particles can be adjusted by cutting by appropriately changing the extrusion speed, pulling speed, cutter speed, etc. during extrusion of the resin molten kneaded product.

[0196] After the resin particles are prepared as described above, the resin particles are dispersed in a dispersion medium. The operation of dispersing the resin particles in the dispersion medium may be performed in a sealed container used in the foaming step described later, or may be performed in a container different from the sealed container used in the foaming step. From the viewpoint of simplifying the manufacturing process, it is preferred to perform the dispersion process in a sealed container used in the foaming step.

[0197] As the dispersion medium, an aqueous dispersion medium with water as the main component is used. In the aqueous dispersion medium, in addition to water, a hydrophilic organic solvent such as ethylene glycol, glycerol, methanol, ethanol, etc. may also be included. The proportion of water in the aqueous dispersion medium is preferably 60% by mass or more, more preferably 70% by mass or more, and further preferably 80% by mass or more.

[0198] It is preferred to add a dispersant to the dispersion medium. By adding a dispersant to the dispersion medium, the welding of the resin particles heated in the container can be suppressed during the foaming process. The amount of the dispersant added is preferably 0.001 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the resin particles. As the dispersant, an organic dispersant or an inorganic dispersant can be used. From the perspective of ease of operation, particulate inorganic substances are preferably used as the dispersant. More specifically, as the dispersant, for example, clay minerals such as alumina, kaolin, mica, and clay, aluminum oxide, titanium oxide, basic magnesium carbonate, basic zinc carbonate, calcium carbonate, iron oxide, etc. can be used. These dispersants can be used alone or in combination of two or more dispersants. Among them, as the dispersant, clay minerals are preferably used. The clay mineral can be a natural clay mineral or a synthetic clay mineral.

[0199] When a dispersant is used, an anionic surfactant such as sodium dodecylbenzenesulfonate, sodium alkylbenzenesulfonate, sodium lauryl sulfate, sodium oleate, etc. is preferably used in combination as a dispersant. The amount of the dispersant added is preferably 0.001 parts by mass or more and 1 part by mass or less relative to 100 parts by mass of the resin particles.

[0200] After the resin particles are dispersed in the dispersion medium, the foaming agent is impregnated in the resin particles in a closed container. The foaming agent impregnated in the resin particles is preferably a physical foaming agent. As the physical foaming agent, inorganic physical foaming agents such as carbon dioxide, air, nitrogen, helium, argon, aliphatic hydrocarbons such as propane, butane, hexane, cyclopentane, cyclohexane, chlorofluoromethane, trifluoromethane, 1,1-difluoromethane, 1-chloro-1,1-dichloroethane, 1,2,2,2-tetrafluoroethane, chloromethane, chloroethane, halogenated hydrocarbons such as dichloromethane and organic physical foaming agents can be listed. These physical foaming agents can be used alone or in combination with two or more physical foaming agents. In addition, inorganic physical foaming agents and organic physical foaming agents can also be used in combination. From the perspective of environmental load and operability, it is preferred to use an inorganic physical foaming agent, and carbon dioxide is more preferred.

[0201] The amount of the foaming agent added is preferably 0.1 parts by mass or more and 30 parts by mass or less, and more preferably 0.5 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the resin particles.

[0202] In the manufacturing process of the foamed beads, as a method for impregnating the resin particles with the foaming agent, a method can be adopted in which the foaming agent is supplied into a closed container, the pressure in the closed container is increased, and the foaming agent is impregnated into the resin particles in the dispersion medium. In this case, by heating the resin particles together with the dispersion medium, the impregnation of the foaming agent into the resin particles can be further promoted.

[0203] The pressure in the closed container during foaming is preferably more than 0.5MPa(G) with a gauge pressure. On the other hand, the pressure in the closed container is preferably less than 4.0MPa(G) with a gauge pressure. If within the above range, there is no hidden danger such as damage or explosion of the closed container, and the foaming particles can be safely manufactured.

[0204] Furthermore, when the dispersion medium is heated, the temperature during foaming can also be set to an appropriate range by raising the temperature of the dispersion medium at 1 to 5° C. / min.

[0205] After the impregnation of the foaming agent into the resin particles is completed, the contents of the sealed container are released into an environment with a lower pressure than the sealed container. As a result, the core layer of the resin particles foams to form a cell structure, and is cooled by the external air to stabilize the cell structure, thereby obtaining foamed particles.

[0206] When the base resin of the core layer is a crystalline thermoplastic resin, it is preferred to heat and foam in the following manner when the foaming agent is impregnated. That is, first, a primary holding step is performed at a temperature above (melting point of crystalline thermoplastic resin - 20°C) and below (melting end temperature of crystalline thermoplastic resin) for a sufficient time, preferably for about 10 to 60 minutes, and then, the temperature is adjusted from (melting point of crystalline thermoplastic resin - 15°C) to a temperature below (melting end temperature of crystalline thermoplastic resin + 10°C). Then, as needed, a secondary holding step is performed at this temperature for a further sufficient time, preferably for about 10 to 60 minutes. Afterwards, it is preferred to release the contents of the sealed container to the outside while the temperature in the sealed container is above (melting point of crystalline thermoplastic resin - 10°C) to foam the resin particles. The temperature in the sealed container during foaming is more preferably above (melting point of crystalline thermoplastic resin) and below (melting point of crystalline thermoplastic resin + 20°C). By heating and foaming the resin particles in this manner, secondary crystals are formed in the crystalline thermoplastic resin constituting the foamed layer, and foamed particles having excellent mechanical strength and excellent moldability can be easily obtained.

[0207] In the preparation of the molded body, the foamed particles obtained as above can also be used directly. In addition, the foamed particles obtained by the above-mentioned direct foaming method can be further foamed, and the foamed particles with increased stacking ratio can be used to prepare the molded body. In addition, when the resin particles are foamed in two stages like this, the foaming process of the first stage is called the primary foaming process, and the foamed particles obtained by the primary foaming process are called primary foamed particles. In addition, the foaming process of the second stage is called the secondary foaming process. The foamed particles obtained by the secondary foaming process are sometimes also called secondary foamed particles.

[0208] The method of increasing the stacking ratio of foamed particles by secondary foaming is, for example, as described below. First, as a primary foaming process, the resin particles are foamed by the above-mentioned direct foaming method to obtain primary foamed particles. Thereafter, internal pressure is applied to the primary foamed particles. More specifically, after the primary foamed particles are placed in a pressure-resistant container, the pressure-resistant container is pressurized using an inorganic gas such as air or carbon dioxide, so that the inorganic gas is impregnated into the foamed particles. Thus, the pressure inside the bubbles of the primary foamed particles is made to be above atmospheric pressure. Thereafter, the primary foamed particles taken out of the pressure-resistant container are heated using a heating medium such as steam or heated air in an environment with a lower pressure than the pressure inside the bubbles, thereby further foaming the primary foamed particles.

[0209] Example

[0210] Examples of the foamed beads, the foamed bead molded article, and the method for producing the same will be described.

[0211] (Thermoplastic resin)

[0212] Table 1 shows the properties of the polypropylene resin and polyamide resin used as thermoplastic resins in the manufacture of the foamed particles. The ethylene-propylene copolymer and ethylene-propylene-butene copolymer used in this example are both random copolymers. The density of PP1 shown in Table 1 is 900 kg / m 3 In addition, the density of PA1 shown in Table 1 is 1120 kg / m 3 In addition, PA1 is a product name manufactured by Ube Industries, Ltd.: UBE Nylon 6434B.

[0213] Table 1

[0214]

[0215] <Monomer Content of Polypropylene Resin>

[0216] The monomer content of the polypropylene resin (specifically, ethylene-propylene copolymer, ethylene-propylene-butene copolymer) is determined by a known method determined by using IR spectroscopy. Specifically, it is determined by the method described in the Handbook of Polymer Analysis (edited by the Polymer Analysis Research Symposium of the Japanese Society of Analytical Chemistry, published in January 1995, publisher: Kinokuniya Bookstore, page numbers and item names: 615-616 "II.2.32.3.4 Propylene / ethylene copolymer", 618-619 "II.2.32.3.5 Propylene / butene copolymer"), that is, a method of quantitatively determining the relationship between the value obtained by correcting the absorbance of ethylene and butene with a predetermined coefficient and the thickness of a film-like test piece.

[0217] More specifically, first, a polypropylene resin was heat-pressed in an environment of 180° C. to form a film, and a plurality of test pieces of different thicknesses were prepared. Next, the IR spectrum of each test piece was measured to read the 722 cm-1 wavelength derived from ethylene. -1 and 733cm -1 The absorbance at 722 , A 733 ) and 766cm from butene -1 The absorbance at 766 ). Next, for each test piece, the ethylene content in the polypropylene resin (unit: mass %) was calculated using the following formulas (6) to (8). The value obtained by arithmetic averaging the ethylene content obtained for each test piece was taken as the ethylene content in the polypropylene resin (unit: mass %).

[0218] (Kˊ 733 )c=1 / 0.96{(Kˊ 733 )a-0.268(Kˊ 722 )a}···(6)

[0219] (Kˊ 722 )c=1 / 0.96{(Kˊ 722 )a-0.150(Kˊ 733 )a}···(7)

[0220] Ethylene content = 0.575 {(K' 722 )c+(K′ 733 )c}···(8)

[0221] Among them, K′ in formulas (6) to (8) a is the apparent absorption coefficient (K′) at each wave number a =A / ρt), K′ c is the corrected absorption coefficient, A is the absorbance, and ρ is the density of the resin (unit: g / cm3 ), t is the thickness of the film-like test piece (unit: cm). In addition, the above formulas (6) to (8) can be applied to random copolymers.

[0222] The butene content (unit: mass %) in the polypropylene resin was calculated for each test piece using the following formula (9). The arithmetic average of the butene content obtained for each test piece was taken as the butene content (unit: mass %) in the polypropylene resin.

[0223] Butene content = 12.3 (A 766 / L)···(9)

[0224] In the formula (9), A is the absorbance, and L is the thickness of the film-like test piece (unit: mm).

[0225] <Flexural modulus of thermoplastic resin>

[0226] Thermoplastic resin was hot pressed at 230°C to produce a 4 mm sheet, from which a test piece of 80 mm in length × 10 mm in width × 4 mm in thickness was cut. The bending elastic modulus of the test piece was determined in accordance with JIS K7171: 2008. In addition, the radius R1 of the indenter and the radius R2 of the support were both 5 mm, the distance between the fulcrums was 64 mm, and the test speed was 2 mm / min.

[0227] <Melting Point of Thermoplastic Resin>

[0228] The melting point of the thermoplastic resin is determined based on JIS K7121:1987. Specifically, first, based on "(2) The case where the melting temperature is measured after a certain heat treatment" described in JIS K7121:1987, the state of the test piece composed of the thermoplastic resin is adjusted. The test piece after the state adjustment is heated from 30°C to 200°C at a heating rate of 10°C / min, thereby obtaining a DSC curve. Then, the top temperature of the melting peak that appears in the DSC curve is taken as the melting point. In addition, as a measuring device, a heat flux differential scanning calorimeter (manufactured by SII Nano Technology Co., Ltd., model: DSC7020) is used.

[0229] <Melt Mass Flow Rate of Thermoplastic Resin>

[0230] The melt mass flow rate (ie, MFR) of the thermoplastic resin is measured in accordance with JIS K7210-1:2014 under the conditions of a temperature of 230° C. and a load of 2.16 kg.

[0231] Next, the structure and production method of the foamed beads used in this example will be described.

[0232] (Foaming particles A)

[0233] As shown in Table 2, the foamed beads A have a multilayer structure, which includes a foamed layer 3 with PP1 (see Table 1) as a base resin, and a non-foamed weldability improving layer 4 with PP2 (see Table 1) as a base resin and covering the foamed layer 3. Figure 6 as well as Figure 7 As shown, the foamed beads A have a cylindrical shape having a through hole 211 as a defect 21. The side circumference of the foamed beads A is covered with a fusion-improving layer 4, and the inside of the fusion-improving layer 4 is composed of a foamed layer 3.

[0234] When making foamed particles A, first, a coextrusion device having a core layer forming extruder, a weldability improving layer forming extruder, and a coextrusion die connected to the two extruders is used, and the extrudate extruded from the coextrusion device is cut by wire cutting to make multilayer resin particles with through holes. Specifically, PP1 and a bubble regulator shown in Table 1 are supplied to the core layer forming extruder, and melt-kneaded at a maximum setting temperature of 245°C in the extruder to obtain a core layer forming resin melt-kneaded product. In addition, zinc borate is used as a bubble regulator, and the amount of zinc borate added is set to 500 mass ppm relative to the polypropylene resin.

[0235] In addition, PP2 shown in Table 1 was melt-kneaded at a maximum set temperature of 245°C in an extruder for forming a weldability-improving layer to obtain a melt-kneaded resin for forming a weldability-improving layer. These melt-kneaded resins were co-extruded and merged in a die head, thereby forming a cylindrical composite consisting of a non-foamed cylindrical core layer and a non-foamed weldability-improving layer covering the outer surface of the cylindrical core layer. After the composite was extruded from a die head having a small hole for forming a through hole in the core layer, the extrudate was pulled while being cooled with cold water at a water temperature of 10°C, and cut into appropriate lengths using a pelletizer, thereby obtaining a multilayer resin pellet consisting of a cylindrical core layer having a through hole and a weldability-improving layer covering the core layer. The mass ratio of the core layer to the weldability-improving layer in the multilayer resin pellet was set to core layer: weldability-improving layer = 95:5 (i.e., the mass ratio of the weldability-improving layer was 5%). In addition, the mass of each multilayer resin pellet was about 1.5 mg.

[0236] Next, the multilayer resin particles were foamed by a direct foaming method to obtain foamed particles A. Specifically, 1 kg of the multilayer resin particles were put into a 5L sealed container together with 3L of water as a dispersion medium. Next, 0.3 parts by mass of a dispersant and 0.004 parts by mass of a dispersant were added to the sealed container relative to 100 parts by mass of the multilayer resin particles, and the multilayer resin particles were dispersed in the dispersion medium. Kaolin was used as the dispersant. In addition, a surfactant (sodium alkylbenzene sulfonate) was used as the dispersant.

[0237] Afterwards, carbon dioxide as a physical foaming agent is supplied into the sealed container while stirring the sealed container, so that the temperature in the container rises to 147.0°C. The pressure in the container at this time (i.e., impregnation pressure, carbon dioxide pressure) is 3.7MPa(G) in gauge pressure. After the temperature in the container reaches 147.0°C, the temperature is maintained for 15 minutes, thereby impregnating the multilayer resin particles with the physical foaming agent. After the impregnation of the physical foaming agent is completed, the sealed container is opened and the contents are released under atmospheric pressure, thereby foaming the multilayer resin particles. By the above, foamed particles A having a foaming layer formed by foaming a core layer and a non-foamed weldability improvement layer covering the foaming layer are obtained.

[0238] (Foaming particles B)

[0239] As shown in Table 2, the foamed particles B have a single-layer structure consisting of a foamed layer 3 with PP1 (see Table 1) as a base resin. That is, the foamed particles B do not have a weldability improving layer. Figure 2 as well as Figure 3 As shown, the foamed beads B have a cylindrical shape having a through hole 211 as a defect 21. The method for producing the foamed beads B is the same as the method for producing the foamed beads A except that the fusion-improving layer 4 is not provided in the production process of the resin beads.

[0240] (Foaming particles C)

[0241] Foamed particles C are cylindrical in shape without through holes and without grooves on the side circumference. That is, foamed particles C do not have defects. When making foamed particles C, first, cylindrical resin particles having a core layer with PP1 as a base resin and a weldability improvement layer with PP2 as a base resin and without defects are made (see Table 2). The resin particles are foamed under the same conditions as foamed particles A, except that the temperature in the container is 150.1°C and the gauge pressure is 2.6MPa (G), thereby producing primary foamed particles. Next, the primary foamed particles are placed in a pressure-resistant container, and the pressure container is pressurized with air, thereby impregnating the air into the bubbles and increasing the internal pressure in the bubbles of the primary foamed particles. Thereafter, the primary foamed particles are taken out of the pressure-resistant container, steam is blown to the foamed particles, and they are heated at atmospheric pressure to obtain foamed particles C having the bulk density recorded in Table 2.

[0242] (Foaming particles D)

[0243] The foamed particles D have a cylindrical shape in which the average pore diameter of the through holes as the defective part is larger than that of the foamed particles A. When the foamed particles D are produced, first, a co-extrusion die having a small hole inner diameter of a die for forming through holes in the core layer is used, which is different from the co-extrusion die used in the production of the foamed particles A, to produce cylindrical resin particles having a core layer with PP1 as a base resin and a weldability improving layer with PP2 as a base resin (see Table 2). The resin particles are foamed under the same conditions as the foamed particles A, except that the temperature in the container is 146.4°C and the gauge pressure is 3.5 MPa (G), thereby obtaining the foamed particles D.

[0244] (Foaming particles E)

[0245] As shown in Table 2, the foamed beads E have a single-layer structure consisting of a foamed layer 3 with PA1 (see Table 1) as a base resin. Figure 2 as well as Figure 3 As shown, the foamed beads E have a cylindrical shape having a through hole 211 as the defective portion 21 .

[0246] When making foamed particles E, first, an extrusion device equipped with an extruder for forming a core layer is used, and the extrudate extruded from the extruder is cut by a wire cutting method to make resin particles. Specifically, PA1 and a bubble adjuster shown in Table 1 are supplied to an extruder for forming a core layer, and melt-kneaded at a maximum setting temperature of 260°C in the extruder to obtain a molten resin mixture for forming a core layer. After the molten mixture is extruded from a die head equipped with a small hole for forming a through hole in the core layer, the extrudate is towed while being cooled with cold water at a water temperature of 10°C, and cut into appropriate lengths using a granulator, thereby obtaining resin particles consisting of a cylindrical core layer with a through hole. In addition, talc is used as a bubble adjuster, and the amount of talc added is set to 3000 mass ppm relative to the polyamide resin. In addition, the mass of each resin particle is about 1.5 mg.

[0247] Next, the resin particles were foamed by a direct foaming method to obtain foamed particles E. Specifically, 1 kg of the resin particles were put into a 5 L sealed container together with 3 L of water as a dispersion medium. Next, 0.3 parts by mass of a dispersant and 0.004 parts by mass of a dispersant were added to 100 parts by mass of the resin particles in the sealed container to disperse the resin particles in the dispersion medium. Kaolin was used as the dispersant. In addition, a surfactant (sodium alkylbenzene sulfonate) was used as the dispersant.

[0248] Afterwards, carbon dioxide as a physical foaming agent is supplied into the sealed container while stirring the sealed container, so that the temperature in the container rises to 131.0°C. The pressure in the container at this time (i.e., impregnation pressure, carbon dioxide pressure) is 4.0MPa(G) in gauge pressure. After the temperature in the container reaches 131.0°C, the temperature is maintained for 15 minutes, thereby impregnating the physical foaming agent into the resin particles. After the impregnation of the physical foaming agent is completed, the sealed container is opened and the contents are released under atmospheric pressure, thereby foaming the resin particles. Thus, foamed particles E having a foaming layer formed by foaming the core layer are obtained.

[0249] (Foaming particles F)

[0250] The foamed particles F are cylindrical in shape without through holes and without grooves on the side circumference. That is, the foamed particles F do not have defects. The method for manufacturing the foamed particles F is the same as the method for manufacturing the foamed particles E, except that the defects are not provided during the production of the resin particles.

[0251] Next, a molded article was produced by the following method using the above-mentioned expanded beads A to F.

[0252] (Examples 1 to 5 and Comparative Examples 1 to 4)

[0253] First, the foamed particles shown in Tables 3 and 4 are dried at 23°C for 24 hours and then immersed in air to increase the internal pressure, i.e., the pressure inside the bubbles, to the value shown in the "Particle Internal Pressure" column of Tables 3 and 4. In addition, in Example 4 and Comparative Example 2, since the foamed particles are not given internal pressure, the symbol "-" is recorded in the "Particle Internal Pressure" column. The internal pressure of the foamed particles is a value measured as follows. The mass Q (unit: g) of the foamed particle group in a state of increased internal pressure just before being filled into the forming mold and the mass U (unit: g) of the foamed particle group after 48 hours are measured, and the difference between Q and U is taken as the amount of air added W (unit: g). Using these values, the internal pressure of the foamed particles (unit: MPa(G)) is calculated based on the following formula (10).

[0254] P=(W / M)×R×T / V···(10)

[0255] Wherein, M in the formula (10) is the molecular weight of air, R is the gas constant, T is the absolute temperature, and V is the volume obtained by subtracting the volume of the base resin occupied by the foamed particle group from the apparent volume of the foamed particle group (unit: L). In this example, M=28.8 (g / mol), R=0.0083 (MPa·L / (K·mol)), and T=296 (K).

[0256] Next, the mold is filled with foamed particles by the crack filling method (crack filling step). Figure 1 As shown, the forming mold 1 used in this example has a fixed mold 11 and a movable mold 13 that is configured to be reciprocating in one direction relative to the fixed mold 11. In addition, the forming mold 1 is configured to be able to form a forming cavity 12 between the fixed mold 11 and the movable mold 13. The forming cavity 12 in the forming mold of this example is configured to be able to form a rectangular forming body with an outer dimension of 300 mm in length × 250 mm in width × 20 mm in thickness, and is arranged in a manner such that the thickness direction of the forming body is along the opening and closing direction of the forming mold 1. The average length L of the forming cavity in the opening and closing direction is represented by the following formula (2): A As shown in Table 3 and Table 4.

[0257] L A =V / S···(2)

[0258] Wherein, V in the formula (2) is the volume of the molding cavity when the molding die is completely closed (unit: mm 3 ), S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold (unit: mm 2 ).

[0259] In the crack filling process, Figure 1As shown in FIG. 1 , in a state where the forming mold is opened so that the size of the crack gap δ (unit: mm), that is, the distance in the opening and closing direction from the fixed mold 11 to the movable mold 13 when the foamed particles are filled, is the value shown in Table 3 and Table 4, the foamed particles 2 are supplied from the hopper 14 to the forming mold 1. After the filling of the foamed particles 2 into the forming cavity 12 is completed in a state where the crack gap is formed between the fixed mold 11 and the movable mold 13, as shown in FIG. Figure 3 As shown in FIG. 1 , the forming die 1 is completely closed to mechanically compress the foamed beads 2. The filling rate F of the foamed beads and the maximum value P of the compression rate at this time are max The values ​​are shown in Tables 3 and 4. In addition, the filling rate F of the foamed beads and the maximum value P of the compression rate max It is calculated by the following formula (1) and formula (3).

[0260] F={a / (b×c)}×100···(1)

[0261] P max =(δ / L min )×100···(3)

[0262] Wherein, a in the formula (1) is the mass of the foamed particles filled in the forming mold (unit: kg), and b is the bulk density of the foamed particles (unit: kg / m 3 ), c is the volume of the forming cavity (unit: m 3 ). In addition, L in the formula (3) min It is the minimum value of the length of the molding cavity in the opening and closing direction when the molding die is completely closed (unit: mm). In addition, the molding die used in this example is configured to be able to mold a rectangular molding body, and is arranged in a manner such that the thickness direction of the molding body is along the opening and closing direction of the molding die 1. Therefore, the minimum value of the length of the molding cavity in the opening and closing direction is L min It is equal to the inner dimension of the molding cavity in the thickness direction of the molded body (that is, the thickness of the obtained molded body).

[0263] After the forming mold is completely closed, a venting process is performed by supplying steam from both sides of the forming mold for 5 seconds for preheating. After that, steam is supplied from one side of the forming mold to heat one side until a pressure of 0.08MPa(G) lower than the forming pressure during the formal heating shown in Tables 3 and 4 is reached. Next, steam is supplied from the other side of the forming mold to heat one side until a pressure of 0.04MPa(G) lower than the forming pressure during the formal heating is reached. After that, steam is supplied from both sides of the forming mold to heat the mold until the forming pressure shown in Tables 3 and 4 is reached. After the formal heating is completed, the pressure in the forming mold is released, and the molded body is cooled in the forming mold until the surface pressure of the molded body based on the foaming force reaches 0.04MPa(G). After that, the molded body is taken out from the forming mold. The molded body after demolding is left to stand in an oven at 80°C for 12 hours to perform a curing process. After the curing process, the molded body is left to stand for 24 hours under the conditions of relative humidity of 50%, 23°C, and 1atm to adjust the state of the molded body. The molded body obtained in this way was subjected to the evaluation of the molded body described later.

[0264] (Example 6, Comparative Example 5)

[0265] In Example 6 and Comparative Example 5, the foamed particles shown in Table 3 and Table 4 were used, and a forming mold 1 was used that was capable of forming a rectangular forming body with outer dimensions of 300 mm in length × 250 mm in width × 60 mm in thickness. Except for this, the forming body was produced by the same method as in Example 1.

[0266] (Example 7, Comparative Example 6)

[0267] In Example 7 and Comparative Example 6, as shown in Tables 3 and 4, the molded body was produced by the same method as in Example 1, except that polyamide resin foamed particles were used and the outer dimensions of the molding cavity in the molding mold were set to 300 mm in length × 250 mm in width × 40 mm in thickness.

[0268] The characteristics of the foamed beads and the molded bodies in the embodiments and comparative examples are shown in Tables 2 to 4. The evaluation methods of the characteristics shown in Tables 2 to 4 are as follows. In addition, the foamed beads of the molded body of Comparative Example 4 were not welded, and a molded body of the desired shape could not be obtained, so no evaluation other than the welding rate was performed. Therefore, the symbol "-" indicating that no evaluation was performed is recorded in the column of each evaluation item in Comparative Example 4. In addition, since Comparative Examples 1 to 2 and Comparative Examples 5 to 6 have poor productivity, the dimensional stability in the case of omitting the curing process was not evaluated. Therefore, in the dimensional stability column of Comparative Examples 1 to 2 and Comparative Examples 5 to 6, the symbol "-" indicating that no evaluation was performed is recorded.

[0269] (Evaluation of Foamed Particles)

[0270] For the measurement and evaluation of physical properties of the expanded beads, the expanded beads were conditioned by standing for 24 hours under the conditions of a relative humidity of 50%, 23° C., and 1 atm.

[0271] <Bulk Density>

[0272] The foamed beads after the state adjustment are filled into the graduated cylinder in a natural stacking manner, and the stacking volume (unit: L) of the foamed beads group is read from the scale of the graduated cylinder. Then, the mass of the foamed beads group in the graduated cylinder (unit: g) is divided by the above-mentioned stacking volume, and the unit is further converted to calculate the bulk density of the foamed beads (unit: kg / m 3 ).

[0273] <Apparent density>

[0274] After measuring the mass of the foamed particle group after the state adjustment, use a metal mesh to sink it into a measuring cylinder filled with ethanol at a temperature of 23°C. Then, taking into account the volume of the metal mesh, the volume of the foamed particle group read out according to the amount of water level rise is measured. After dividing the mass of the foamed particle group obtained in this way (unit: g) by the volume (unit: L), the units are converted to calculate the apparent density of the foamed particles (unit: kg / m 3 ). In addition, the column "Apparent density / bulk density" in Table 2 shows the ratio of the apparent density to the bulk density obtained by the above method.

[0275] Average diameter of through holes d

[0276] The average pore size d of the through holes of the foamed particles is calculated as follows. First, the foamed particle group is allowed to stand for more than 24 hours in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1 atm to adjust the state of the foamed particles. For 100 foamed particles randomly selected from the foamed particle group after state adjustment, they are cut at the center of the axial direction with a plane perpendicular to the axial direction, thereby exposing the cut surface. Take a photo of the cut surface of each foamed particle, and calculate the cross-sectional area (opening area) of the through hole portion in the cross-sectional photo. Calculate the diameter of an imaginary circle with the same area as the cross-sectional area, and take the value obtained by arithmetic averaging them as the average pore size d (unit: mm) of the through holes of the foamed particles.

[0277] The average outer diameter D of the foamed particles

[0278] The average outer diameter of the foamed particles is calculated as follows. First, the foamed particle group is allowed to stand for more than 24 hours in an environment of relative humidity of 50%, temperature of 23°C, and air pressure of 1atm to adjust the state of the foamed particles. For 100 foamed particles randomly selected from the foamed particle group after state adjustment, they are cut at the center of the axial direction with a plane perpendicular to the axial direction, thereby exposing the cut surface. A photograph of the cut surface of each foamed particle is taken to calculate the cross-sectional area of ​​the foamed particles (including the opening of the through hole). Calculate the diameter of an imaginary circle with the same area as the cross-sectional area, and take the value obtained by arithmetic averaging them as the average outer diameter D (unit: mm) of the foamed particles. In addition, the value of the ratio d / D of the average pore size d of the through holes of the foamed particles to the average outer diameter D is also recorded in Table 2.

[0279] Average wall thickness of foamed particles t

[0280] The average wall thickness t (unit: mm) of the foamed beads was calculated using the average outer diameter D (unit: mm) of the foamed beads and the average pore diameter d (unit: mm) of the through-holes based on the following formula (5). In addition, Table 2 also lists the value of the ratio t / D of the average wall thickness t of the foamed beads to the average outer diameter D.

[0281] t=(Dd) / 2···(5)

[0282] <Total cross-sectional area Ct of defects, average cross-sectional area Ca of each defect>

[0283] 100 foamed beads are randomly selected from the foamed bead group after the state adjustment, and these foamed beads are cut at the center of the axial direction with a plane perpendicular to the axial direction to expose the cut surface. Then, a photograph of the cut surface of the foamed beads is taken, and the image is analyzed to measure the cross-sectional area C of the through hole of each foamed bead (refer to Figure 3 as well as Figure 7 ).

[0284] The above operation is performed on 100 foamed beads, and the arithmetic mean of the total cross-sectional area of ​​the through holes obtained is taken as the total cross-sectional area Ct of the defective parts. In addition, in the foamed beads A, the foamed beads B and the foamed beads D, since each foamed bead is provided with a through hole, the average cross-sectional area Ca of each defective part is equal to the total cross-sectional area Ct of the defective parts. In Table 2, the ratio Ct / A of the total cross-sectional area Ct of the defective parts in the cut surface to the average cross-sectional area A of the foamed beads and the ratio Ca / A of the average cross-sectional area Ca of each defective part to the average cross-sectional area A of the foamed beads are recorded.

[0285] In addition, the calculation method of the average cross-sectional area A of the above-mentioned foamed particles is as follows. First, the foamed particles are cut at the center of their axial direction with a plane perpendicular to the axial direction to expose the cut surface. The cross-sectional area of ​​the foamed particles 2 in the cut surface is measured. The cross-sectional area of ​​the foamed particles 2 is the sum of the cross-sectional area of ​​the foamed layer 3 and the cross-sectional area of ​​the weldability improvement layer 4 in the cut surface. The measurement of the cross-sectional area of ​​the foamed particles 2 in the cut surface is performed by taking a photograph of the cut surface of the foamed particles and performing image analysis. The cross-sectional area of ​​the defective portion is not included in the cross-sectional area of ​​the foamed particles. The above operation is performed on 100 foamed particles, and the arithmetic mean of the cross-sectional areas of the obtained foamed particles is taken as the average cross-sectional area A of the foamed particles.

[0286] <Productivity Evaluation>

[0287] The productivity of the molded body is evaluated based on the cycle time in the internal pressure application process, the cycle time in the mold forming process, and the cycle time in the drying process for drying the molded body after demolding. Specifically, when the cycle time in the internal pressure application process, the cycle time in the mold forming process, and the cycle time in the drying process for drying the molded body after demolding are all good as determined below, the productivity is determined to be excellent and recorded as "A" in the "Comprehensive Evaluation" column of Tables 3 and 4. On the other hand, when any of the above three evaluations is poor, the productivity is determined to be poor and recorded as "B" in the "Comprehensive Evaluation" column of Tables 3 and 4.

[0288] · Cycle time in the internal pressure application process

[0289] When a good molded body can be obtained without applying internal pressure to the foamed beads or by applying an internal pressure of less than 0.1 MPa (G) to the foamed beads, the cycle time in the internal pressure applying step is judged to be good, and "good" is recorded in the "Internal pressure applying cycle" column of Tables 3 and 4. On the other hand, when a good molded body cannot be obtained when the internal pressure applied to the foamed beads is 0.1 MPa (G) or less, the cycle time in the internal pressure applying step is judged to be long and the productivity is poor, and "poor" is recorded in the "Internal pressure applying cycle" column of Tables 3 and 4.

[0290] Cycle time in the in-mold forming process

[0291] When the foamed particles are molded in-mold, the time from the time point when the formal heating is completed to the time point when the surface pressure of the molded body based on the foaming force reaches 0.04MPa (G) is measured, and this time is taken as the cooling time. When the cooling time is less than 50 seconds, it is judged that the cycle time in the mold forming process is good, and it is recorded as "good" in the "molding cycle" column of Table 3 and Table 4. On the other hand, when the cooling time is greater than 50 seconds, it is judged that the cycle time in the mold forming process is long and the productivity is poor, and it is recorded as "poor" in the "molding cycle" column of Table 3 and Table 4.

[0292] Cycle time in the drying process

[0293] The moisture content of the molded body after the mold was released from the molding die and dried in an atmosphere at 80° C. for 1 hour was measured. When the moisture content of the molded body after drying was 3% or less, the cycle time in the drying process was judged to be good, and it was recorded as "good" in the "Drying Cycle" column of Tables 3 and 4. On the other hand, when the moisture content of the molded body after drying was greater than 3%, it was judged that the cycle time in the drying process was long and the productivity was poor, and it was recorded as "poor" in the "Drying Cycle" column of Tables 3 and 4.

[0294] (Evaluation of Molded Body)

[0295] <Molding Density>

[0296] The density of the molded body (unit: kg / m) was calculated by dividing the mass of the molded body (unit: g) by the volume (unit: L) obtained from the outer dimensions of the molded body and converting the units. 3 ).

[0297] <Weldability>

[0298] The molded body is bent in a manner that is roughly equally divided in the long side direction to break it. Afterwards, the fracture surface of the test piece is observed, and the number of foamed particles whose foamed particles themselves are broken (material damage) and the number of foamed particles peeled off between the interfaces of the foamed particles are measured by visual inspection. Then, the ratio of the number of foamed particles whose material is damaged to the total number of foamed particles present on the fracture surface is calculated, and the value expressed as a percentage is used as the welding rate of the molded body (unit: %). In the "Fusibility" column of Tables 3 and 4, when the welding rate of the test piece is 90% or more, the mark "A" is recorded, when it is 70% or more and less than 90%, the mark "B" is recorded, and when it is less than 70%, the mark "C" is recorded.

[0299] <Surface Properties>

[0300] The surface of the molded body was visually observed, and the surface properties of the molded body were evaluated based on the following criteria.

[0301] A: The surface of the molded body has a good surface condition in which there are few intergranular gaps and irregularities due to grooves, through holes, etc. are not noticeable.

[0302] B: Concavities and convexities due to inter-particle gaps and / or grooves, through holes, etc. are slightly observed on the surface of the molded product.

[0303] C: Concavities and convexities due to inter-particle gaps and / or grooves, through holes, etc. are clearly observed on the surface of the molded body.

[0304] <Shape stability when curing process is omitted>

[0305] After removing the molded body from the forming mold, the shape stability is evaluated using the molded body that has not been subjected to the curing process. Specifically, the molded body after demolding is left to stand for 24 hours under the conditions of a relative humidity of 50%, 23°C, and 1atm, thereby adjusting the state of the molded body. When observing the molded body after the state adjustment from the top view in the thickness direction, the thickness of the molded body at four locations 10 mm inward from each vertex to the center direction and the thickness of the molded body in the central part are measured respectively. Next, the ratio of the thickness of the thinnest part of the measured parts to the thickness of the thickest part is calculated (unit: %). In the "Shape Stability" column of Tables 3 and 4, when the thickness ratio is 95% or more, it is recorded as "good", and when it is less than 95%, it is recorded as "poor".

[0306]

[0307]

[0308]

[0309] As shown in Table 2, the foamed particles A, foamed particles B, and foamed particles E used in the examples have the specific shapes. In addition, as shown in Table 3, in Examples 1 to 7, the foamed particles are filled in the cracks in such a manner that the filling rate F is within the specific range, and then in-mold molding is performed. Therefore, in Examples 1 to 7, the cycle time in the internal pressure application process, the cycle time in the in-mold molding process, and the cycle time in the drying process can be shortened, thereby improving the productivity of the molded body. In addition, the molded bodies of Examples 1 to 7 have excellent surface properties and weldability, and can suppress significant shrinkage and deformation even when the curing process is omitted. On the other hand, the foamed particles B with a single-layer structure undergo significant shrinkage and deformation when the curing process is omitted.

[0310] On the other hand, as shown in Table 2, the foamed beads C used in Comparative Example 1 are conventional polypropylene resin foamed beads without defects. In addition, the foamed beads F used in Comparative Example 6 are conventional polyamide resin foamed beads without defects. If the foamed beads C and the foamed beads F are molded after the cracks are filled so that the filling rate F is within the specific range, the cycle time in the mold molding process becomes long as shown in Table 4.

[0311] As shown in Table 2, in the expanded beads D used in Comparative Example 2, the ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the expanded beads and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the expanded beads are too large. If such expanded beads D are molded in-mold after crack filling, the cycle time in the drying process increases due to the insufficient secondary foaming of the expanded beads and the large defects, as shown in Table 4. In addition, the surface properties of the obtained molded body deteriorate.

[0312] Comparative Example 3 is an example in which the size δ of the cleft gap is narrowed and the filling rate F is reduced compared to Example 1. As shown in Table 4, when the cleft filling and in-mold forming are performed under the conditions of Comparative Example 3, the moisture content of the molded body after demolding becomes high, resulting in an increase in the cycle time in the drying process.

[0313] Comparative Example 4 is an example in which the size of the cleft gap δ is increased and the filling rate F is increased compared with Example 2. As shown in Table 4, when the cleft gap is filled and molded under the conditions of Comparative Example 4, the foamed particles in the mold are excessively compressed and the foamed particles are hardly fused to each other.

[0314] Comparative Example 5 is an example of in-mold molding of conventional polypropylene resin foamed particles (foamed particles C) using the same molding die as Example 6. As shown in Table 4, under the molding conditions of Comparative Example 5, the time required for cooling in the molding die becomes longer. In addition, the fusion rate of the obtained molded body becomes lower.

[0315] The specific method of manufacturing the thermoplastic resin foamed particle molded body involved in the present invention is described above based on the embodiments, but the specific method of manufacturing the thermoplastic resin foamed particle molded body involved in the present invention is not limited to the embodiment, and the structure can be appropriately changed within the scope of not damaging the main purpose of the present invention.

Claims

1. A method for producing a thermoplastic resin foamed particle molded body, wherein: The method for producing the thermoplastic resin foamed particle molded body comprises: a crack filling step of filling the molding cavity of the molding die with the crack gap opened with thermoplastic resin foamed particles having a foam layer, and then completely closing the molding die; and In the in-mold forming process, after the crack filling process is completed, steam is supplied into the forming cavity to fuse the foamed particles to each other, thereby producing a foamed foam with a strength of 10 kg / m 3 Above and 150kg / m 3 A thermoplastic resin foamed particle molded body having a molded body density of The foamed layer is composed of a crystalline thermoplastic resin. The foamed particles have a columnar shape and have one or more defective parts selected from the group consisting of a through hole penetrating the inside thereof in the axial direction and a groove extending in the axial direction on the side circumference thereof, The ratio Ca / A of the average cross-sectional area Ca of each defect to the average cross-sectional area A of the foamed beads in the cross-sectional surface obtained by cutting the foamed beads at the center of the axial direction with a plane perpendicular to the axial direction is 0.01 or more and 0.20 or less, and the ratio Ct / A of the total cross-sectional area Ct of the defects to the average cross-sectional area A of the foamed beads is 0.02 or more and 0.20 or less, In a state where the forming mold is completely closed, the filling rate F of the foamed beads represented by the following formula (1) is 125% or more and 220% or less, F={a / (b×c)}×100%···(1) Wherein, a in the formula (1) is the mass of the foamed particles filled in the forming mold, in kg, and b is the bulk density of the foamed particles, in kg / m 3 , c is the volume of the forming cavity, in m 3 .

2. The method for producing a thermoplastic resin foamed particle molded article according to claim 1, wherein: The average length L of the molding cavity in the opening and closing direction of the molding die is represented by the following formula (2): A 10 mm or more and 200 mm or less, L A =V / S···(2) Wherein, V in the formula (2) is the volume of the forming cavity when the forming mold is completely closed, and the unit is mm 3 , S is the projection area of ​​the forming cavity when projecting the forming cavity in the opening and closing direction of the forming mold, in mm 2 .

3. The method for producing a thermoplastic resin foamed particle molded body according to claim 1 or 2, wherein: A ratio of the apparent density of the foamed particles to the bulk density of the foamed particles is greater than 1.6 and less than 2.

0.

4. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The foamed beads have one or more through holes as the defective portions.

5. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The foamed beads include a foamed layer and a weldability improving layer covering the foamed layer. The base resin of the foamed layer is a first crystalline thermoplastic resin, and the base resin of the weldability improving layer is a second thermoplastic resin.

6. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The crystalline thermoplastic resin constituting the foamed layer is a polyolefin-based resin.

7. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The crystalline thermoplastic resin constituting the foamed layer is an ethylene-propylene random copolymer having an ethylene component content of 0.5% by mass or more and 3.5% by mass or less.

8. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The bulk density of the foamed particles is 10 kg / m 3 Above and 50kg / m 3 the following.

9. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The thermoplastic resin foamed particle molded article obtained by the above production method has a void ratio of 4% to 12%.

10. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: The crack filling step is performed using the foamed beads to which no internal pressure is applied or the foamed beads to which an internal pressure of less than 0.1 MPa in gauge pressure is applied.

11. The method for producing a thermoplastic resin foamed particle molded article according to claim 1 or 2, wherein: When the forming die is completely closed, the maximum value P of the compression ratio expressed by the following formula (3) is max is 25% or more and 120% or less, P max =(δ / L min )×100%···(3) Wherein, δ in the formula (3) is the size of the gap of the forming die, in mm, L min It is the minimum value of the length of the molding cavity in the opening and closing direction when the molding die is completely closed, and the unit is mm.

Citation Information

Patent Citations

  • Method for manufacturing in-mold molded foam polypropylene particle

    JP2003201361A

  • Polyolefin-based resin foam particles, polyolefin-based resin foam particle molded body, and production method for polyolefin-based resin foam particles

    WO2020189389A1

  • Polyurethane foam and method for producing same

    CN103562282A

  • Device and method for synthetic resin internal die foam molding and internal die foam molded product obtained by these device and method

    CN1298339A